Polyethylene powder

JP2023156554A5Pending Publication Date: 2025-04-18ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022065981
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-04-13
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Conventional methods for producing polyethylene do not adequately consider the relationship between spherulite structure and performance requirements, leading to suboptimal transparency in films and mechanical strength in fibers and battery separators.

Method used

Control the spherulite structure of polyethylene by adjusting parameters such as average circularity, skewness, and area, along with titanium, magnesium, and silica content, to enhance film transparency, fiber mechanical strength, and battery separator strength.

Benefits of technology

The controlled spherulite structure improves film transparency, fiber mechanical strength, and battery separator mechanical strength, as well as reduces heat shrinkage rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000031_0000
    Figure 00000031_0000
  • Figure 00000031_0001
    Figure 00000031_0001
  • Figure 00000031_0002
    Figure 00000031_0002
Patent Text Reader

Abstract

To provide a polyethylene that has better film transparency, fiber mechanical strength, battery separator mechanical strength and thermal shrinkage.SOLUTION: Provided is a polyethylene powder that has an average circularity of a spherocrystal of 0.3 or more and 0.7 or less and an average skewness of circularity of the spherocrystal of -1 or more and 1 or less for the spherocrystal observed at an extrapolated crystallization start temperature + 2.0°C when processed under a predetermined <processing condition> and observed with an optical microscope the state in which the temperature is increased and the temperature is decreased under a predetermined <measurement condition> using a hot stage.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to polyethylene powder. [Background technology]

[0002] Conventionally, polyethylene has been molded using various molding methods such as melt stretching, injection molding, extrusion molding, and compression molding, and is used in a wide variety of applications including films, sheets, microporous membranes, fibers, foams, and pipes. In recent years, the demand for microporous membranes has grown rapidly, and these microporous membranes are used as separators, which are important components in lithium-ion batteries and lead-acid batteries. The above-mentioned films require high transparency. Furthermore, the above-mentioned fibers require high mechanical strength. Separators for batteries require high mechanical strength.

[0003] A method for producing polyethylene using a so-called Ziegler-Natta type catalyst, consisting of a titanium compound and an organoaluminum compound, is known as a catalyst for producing olefin polymers or copolymers that satisfy these requirements. On the other hand, techniques have also been discovered for obtaining polyethylene by polymerizing ethylene homopolymer or copolymerization of ethylene with other α-olefins with high activity by using a catalyst consisting of a soluble halogen-containing transition metal compound such as bis(cyclopentadienyl)zirconium dichloride and an aluminoxane, which is a type of organoaluminum oxy compound (see, for example, Patent Documents 1 and 2).

[0004] Furthermore, Patent Documents 3 and 4 disclose a method for polymerizing olefins to obtain polyethylene and the like using a catalyst consisting of a cyclopentadienyl metal compound and an ionic compound capable of stabilizing the cyclopentadienyl metal cation. [Prior art documents] [Patent Documents]

[0005] [Patent Document 1] Special Publication No. 4-12283 [Patent Document 2] Publication DE3127133.2 [Patent Document 3] Special Publication No. 1-501950 [Patent Document 4] Special Publication No. 1-502036 [Patent Document 5] Patent No. 6788590 [Overview of the project] [Problems that the invention aims to solve]

[0006] However, the conventional methods for producing polyethylene using catalyst systems proposed in these prior arts did not consider the relationship between the spherulite structure of polyethylene and the required performance described above, leaving room for improvement in terms of film transparency, fiber mechanical strength, and battery separator mechanical strength.

[0007] To solve the above problems, for example, Patent Document 5 discloses a method for providing an ethylene / alpha olefin copolymer with excellent processability and surface properties at a specific molecular weight, molecular weight distribution, density, spherulite diameter, and semi-crystallization time of 123°C, relating the relationship between the spherulite structure of polyethylene and the required performance.

[0008] However, the methods proposed in these improved technologies impose limitations on the polyethylene that can be used due to specific molecular weight, molecular weight distribution, density, spherulite diameter, and semi-crystallization time at 123°C. As mentioned above, there is a constant demand for the manufacture of products with superior physical properties, particularly for the transparency of films, the mechanical strength of fibers, and the mechanical strength of battery separators.

[0009] Therefore, the object of the present invention is to provide polyethylene that has superior transparency of the film, mechanical strength of the fibers, and mechanical strength and thermal shrinkage rate of the battery separator. [Means for solving the problem]

[0010] Therefore, in view of the above circumstances, the inventors have completed the present invention after diligent study. That is, the present invention is as follows. [1] When processing is performed under the following <processing conditions>, and the heating and cooling are performed using a hot stage under the following <measurement conditions>, and the results are observed with an optical microscope, for spherulites observed at the extrapolation crystallization start temperature + 2.0°C, The average circularity of the spherulite is 0.3 or more and 0.7 or less. The average skewness of the circularity of the spherulite is between -1 and 1. Polyethylene powder. <Processing conditions> (1) Compress and mold the polyethylene powder at a temperature above its melting point to a thickness of 1 mm. (2) Cut out a 15 μm thick test piece from the cross-section of the molded product. (3) Place the specimen between a glass slide and a coverslip, and heat again to a temperature above the melting point of the polyethylene powder to obtain a slide for observation. <Measurement conditions> (1) Heat from 30°C to 180°C at a rate of 20°C / min. (2) Hold at 180°C for 5 minutes. (3) Cool the temperature from 180°C to 140°C at a rate of 20°C / min. (4) Cool the temperature from 140°C to 115°C at a rate of 2°C / min. [2] The average area of ​​the spherulites is 20 μm 2 More than 100μm 2 The following is: [1] Polyethylene powder as described above. [3] Titanium content is less than 3 ppm. Polyethylene powder as described in [1] or [2]. [4] The magnesium content is between 10 ppm and less than 200 ppm. Polyethylene powder as described in any of [1] to [3]. [5] Silica content is less than 10 ppm. Polyethylene powder as described in any of [1] to [4]. [6] The molecular weight distribution (Mw / Mn) is less than 4. Polyethylene powder as described in any of [1] to [5]. [Effects of the Invention]

[0011] The present invention makes it possible to provide polyethylene with superior transparency of the film, mechanical strength of the fibers, mechanical strength of the battery separator, and thermal shrinkage rate. [Brief explanation of the drawing]

[0012] [Figure 1] This shows an example of image analysis of spherulites captured with an optical microscope. [Figure 2] This shows an example of image analysis of spherulites captured with an optical microscope. [Figure 3] This shows an example of image analysis of spherulites captured with an optical microscope. [Figure 4] This shows an example of image analysis of spherulites captured with an optical microscope. [Figure 5] This shows an example of image analysis of spherulites captured with an optical microscope. [Figure 6] This shows an example of image analysis of spherulites captured with an optical microscope. [Figure 7] This shows an example of image analysis of spherulites captured with an optical microscope. [Figure 8] This shows an example of image analysis of spherulites captured with an optical microscope. [Modes for carrying out the invention]

[0013] The following describes in detail embodiments for carrying out the present invention (hereinafter also referred to as "this embodiment"). It should be noted that the present invention is not limited to this embodiment and can be implemented in various modifications without departing from its essence.

[0014] [Polyethylene powder] The polyethylene powder of this embodiment is processed under the following <processing conditions>, and when the heating and cooling process is observed with an optical microscope using a hot stage under the following <measurement conditions>, the average circularity of the spherulites observed at the extrapolation crystallization start temperature + 2.0°C is 0.3 or more and 0.7 or less, and the average skewness of the circularity of the spherulites is -1 or more and 1 or less. <Processing conditions> (1) Compress and mold the polyethylene powder at a temperature above its melting point to a thickness of 1 mm. (2) Cut out a 15 μm thick test piece from the cross-section of the molded product. (3) Place the specimen between a glass slide and a coverslip, and heat again to a temperature above the melting point of the polyethylene powder to obtain a slide for observation. <Measurement conditions> (1) Heat from 30°C to 180°C at a rate of 20°C / min. (2) Hold at 180°C for 5 minutes. (3) Cool the temperature from 180°C to 140°C at a rate of 20°C / min. (4) Cool the temperature from 140°C to 115°C at a rate of 2°C / min. In this embodiment, the polyethylene powder exhibits superior transparency in the film formed from the polyethylene powder, superior mechanical strength in the fibers, and superior mechanical strength and thermal shrinkage rate in the battery separator, due to the average circularity and average skewness of the spherulites being within the above range. The polyethylene powder of this embodiment will be described in detail below.

[0015] [Crystal structure of polyethylene] The crystalline structure of polyethylene in this embodiment will be described. Generally, polyethylene, a crystalline polymer, is known to have both crystalline and amorphous structures below its melting point. When molten polyethylene is slowly cooled without rapid cooling, the process of spherulite formation and growth can be observed. As molten polyethylene is slowly cooled, the polymer chains crystallize while extending in a straight shape, repeatedly folding at certain points to form a plate-like microcrystalline structure. This plate-like microcrystalline structure is also called a lamellae.

[0016] The physical properties of the polyethylene crystals in this embodiment will be described in detail below.

[0017] [Average circularity] In the present invention, when polyethylene is processed under the above processing conditions and the temperature is raised and lowered using a hot stage under the above measurement conditions, and observed with an optical microscope, the average circularity of the spherulites observed at the extrapolation crystallization start temperature + 2.0°C (hereinafter also referred to as circularity) is 0.3 to 0.7, preferably 0.3 to 0.6, and more preferably 0.35 to 0.55. When the circularity of the spherulites is within the above range, distorted spherulites are formed as the lamellae elongate. For example, when stretching films, fibers (e.g., high-strength fibers) or separators for secondary batteries (e.g., microporous films), the fracture of the spherulites tends to proceed uniformly, and as a result, the crystals tend to orient easily, and elongated chain crystals tend to form. Furthermore, this increases the degree of crystallinity, resulting in high mechanical strength (puncture strength, tensile strength, etc.) and heat resistance (thermal shrinkage rate, etc.) in materials such as fibers (e.g., high-strength fibers) and separators for secondary batteries (e.g., microporous membranes), and creep resistance in materials such as fibers (e.g., high-strength fibers).

[0018] In this embodiment, circularity is a parameter expressed by the following formula (1) in the cross-sectional structure of polyethylene spherulites, where S is the area of ​​the spherulite and L is the perimeter of the spherulite. Circularity = 4πS / L 2 Formula (1) The closer the spherulite is to a perfect circle, the closer its circularity approaches its maximum value of 1. While there are no particular limitations on the method for observing the cross-sectional structure of polyethylene spherulites, for example, the method described in the examples below can be employed.

[0019] [Average skewness of circularity] In the present invention, when polyethylene is processed under the above-mentioned processing conditions and the temperature is raised and lowered using a hot stage under the above-mentioned measurement conditions, and the resulting changes are observed with an optical microscope, the average skewness of the circularity of the spherulites observed at the extrapolation crystallization start temperature + 2.0°C (hereinafter also referred to as the skewness of circularity) is preferably -1 to 1, more preferably -0.5 to 1, and more preferably 0 to 0.5. When the average strain of the spherulites is within the above range, the spherulites often become distorted as the lamellae elongate. For example, when stretching films, fibers (e.g., high-strength fibers), or separators for secondary batteries (e.g., microporous films), spherulites with low circularity have more points of fracture, so the fracture of the spherulites tends to progress uniformly. As a result, the crystals are more likely to be oriented, and elongated chain crystals are more likely to be formed. Furthermore, the degree of crystallinity increases, and for example, fibers (e.g., high-strength fibers) and separators for secondary batteries (e.g., microporous films) can be made to have high mechanical strength (puncture strength, tensile fracture strength, etc.) and heat resistance (thermal shrinkage rate, etc.), and for example, fibers (e.g., high-strength fibers) can be made to have creep resistance.

[0020] In this embodiment, the average skewness of circularity is the circularity of N spherulites observed in the cross-sectional structure of polyethylene spherulites, respectively, X1, X2...X N This parameter is expressed by the following equation (2), where u is the mean circularity and σ is the standard deviation. Average skewness of circularity = Σ(Xi-μ) 3 / (Nσ 3 ) Formula (2) As the mean skewness of the circularity approaches 0, the distribution of circularity approaches a normal distribution.

[0021] [Area average of polyethylene spherulites] In this invention, the area of ​​polyethylene spherulites (hereinafter also referred to as spherulite area) is 20 to 100 μm².2 It is preferably in the range of, 30 to 80 μm 2 It is more preferably in the range of, 40 to 70 μm 2 It is even more preferably in the above range. When the spherulites are within the above range, since the spherulite size is small, for example, the transparency of the extruded film tends to be high.

[0022] The method for obtaining polyethylene with a small degree of distortion and / or spherulite area of spherulites is not particularly limited. For example, there is a method of uniformly dispersing catalyst residues inside polyethylene particles. Although the mechanism by which the average circularity of spherulites can be controlled within the previous range is not clear, the present inventors estimate as follows.

[0023] Since the catalyst residue is an inorganic substance, it behaves as if there are hard nucleating agents and / or foreign substances inside the molten polyethylene. During the process of crystallization of the molten polyethylene, the residue becomes a nucleating agent for crystal formation and / or a foreign substance during the crystal growth process. Therefore, when the crystal is rapidly formed and / or the molecular chains are aligned and folded, the crystal grows so as to avoid the residue, resulting in spherulites with a distorted shape. In addition, as the number of crystal nuclei increases, the density of the spherulites to be formed increases, and adjacent spherulites collide with each other, causing the spherulite growth to stop early. Therefore, spherulites with a small spherulite area can be obtained.

[0024] The method for uniformly dispersing catalyst residues inside polyethylene particles is not particularly limited. For example, there is a method of increasing the initial activity of polymerization. Generally, it is known that polyethylene catalysts cause fragmentation during polymerization and disperse inside polyethylene particles. Therefore, by performing rapid polymerization at the initial stage of polymerization, the catalyst residue becomes finer than usual, and polyethylene with uniform dispersion can be obtained.

[0025] The method for increasing the initial activity of polymerization is not particularly limited. For example, as the compound of the active site, using a metallocene compound represented by a single-site catalyst has a higher initial activity than titanium tetrachloride represented by a ZN-based catalyst.

[0026] Other methods to increase the initial polymerization activity include, but are not limited to, increasing the amount of active sites supported. A larger amount of active sites shortens the distance between adjacent active sites, and the polymerization heat between them increases the temperature near the active sites, promoting activation and allowing more polyethylene chains to grow. It is preferable that the amount of active sites supported per gram of support be 60 μmol or more, and more preferably 100 μmol or more.

[0027] Other methods for increasing the initial polymerization activity include, but are not limited to, feeding a large amount of catalyst and / or feeding a mixture of the main catalyst and a co-catalyst. When the feed concentration is high and / or the main catalyst and co-catalyst are mixed and fed, the amount of heat generated during polymerization increases locally only immediately after feeding, thus enabling rapid polymerization only in the initial stages.

[0028] Other methods for increasing the initial polymerization activity include, but are not limited to, raising the temperature of the feed catalyst higher than the polymerization temperature of the reactor. This increases the polymerization activity only immediately after feeding, allowing for rapid polymerization only in the initial stage. The temperature difference between the polymerization temperature and the feed catalyst is preferably 5°C or more, and more preferably 15°C or more.

[0029] Other methods to increase the initial polymerization activity include, but are not limited to, drying the catalyst. For reasons that are not entirely clear, catalysts that have been dried and then returned to a slurry state exhibit higher polymerization activity.

[0030] There are no particular limitations on the method for uniformly dispersing the catalyst residue inside the polyethylene particles, but for example, a carrier that is easily broken by polymerization can be used. Generally, silica as a carrier material is hard and difficult to break, so it is preferable to use magnesium chloride or diatomaceous earth compounds as carrier materials.

[0031] One method for uniformly dispersing catalyst residue within polyethylene particles is to create pores on the surface of the catalyst. When polyethylene polymerizes from active sites within the pores on the catalyst surface, stress is applied that tries to expand the pores after they are filled with polyethylene, causing the catalyst to fragment.

[0032] There are no particular limitations on the method for forming pores on the surface of the catalyst, but for example, by swelling a magnesium chloride support with a short-chain alcohol and then contacting it with alkylaluminum, these can be extracted from the system, thereby forming pores in the support and increasing the specific surface area of ​​the support.

[0033] In this embodiment, the polyethylene powder preferably has a molecular weight distribution of less than 4, which is the ratio of the weight-average molecular weight (Mw) to the number-average molecular weight (Mn) (Mw / Mn). The method for measuring the molecular weight distribution is not particularly limited, but for example, the method described in the examples below can be used. When the molecular weight distribution is within the above range, the mechanical strength of the molded article tends to be further improved.

[0034] There are no particular limitations on the method for controlling the molecular weight distribution within the above range, but examples include using metallocene compounds, such as single-site catalysts, as polymerization catalysts.

[0035] [Intrinsic viscosity] The polyethylene powder of this embodiment (hereinafter also simply referred to as "powder") has an intrinsic viscosity IV of 1.0 dL / g or more and 33.0 dL / g or less, preferably 1.5 dL / g or more and 31.0 dL / g or less, and more preferably 2.4 dL / g or more and 29.0 dL / g or less.

[0036] In this embodiment, the polyethylene powder exhibits improved mechanical strength due to its intrinsic viscosity IV being above the lower limit, and improved moldability due to its intrinsic viscosity IV being below the upper limit.

[0037] Furthermore, if the polyethylene powder of this embodiment is used, for example, in a molded body of a separator for secondary batteries, the intrinsic viscosity IV is preferably 1.0 dL / g or more and 13.0 dL / g or less, more preferably 1.5 dL / g or more and 11.5 dL / g or less, and even more preferably 2.4 dL / g or more and 9.5 dL / g or less. Separators for secondary batteries obtained by molding polyethylene powder with an intrinsic viscosity IV within the above range tend to have excellent film strength and thermal shrinkage properties.

[0038] Furthermore, if the polyethylene powder of this embodiment is used, for example, in a molded fibrous body, its intrinsic viscosity IV is preferably 13.5 dL / g or more and 33.0 dL / g or less, more preferably 15.0 dL / g or more and 31.0 dL / g or less, and even more preferably 16.5 dL / g or more and 29.0 dL / g or less. Fibers obtained by molding polyethylene powder with an intrinsic viscosity IV within the above range (for example, molding after general or low-temperature pre-swelling) tend to have excellent yarn strength.

[0039] There are no particular limitations on how to control the intrinsic viscosity IV within the above range, but for example, one can change the polymerization temperature of the reactor when homopolymerizing ethylene or copolymerizing ethylene with an olefin other than ethylene that can copolymerize with ethylene. The intrinsic viscosity IV tends to decrease as the polymerization temperature increases and tends to increase as the polymerization temperature decreases. Another method to bring the intrinsic viscosity IV within the above range is not particularly limited, but for example, one can change the type of organometallic compound used as a co-catalyst when homopolymerizing ethylene or copolymerizing ethylene with an olefin that can copolymerize with ethylene. Furthermore, another method to bring the intrinsic viscosity IV within the above range is not particularly limited, but for example, one can add a chain transfer agent when homopolymerizing ethylene or copolymerizing ethylene with an olefin that can copolymerize with ethylene. By adding a chain transfer agent, the intrinsic viscosity IV of the resulting polyethylene tends to decrease even at the same polymerization temperature. In this embodiment, the intrinsic viscosity IV can be determined by the method described in the examples below.

[0040] The polyethylene powder of this embodiment is preferably a powder consisting of an ethylene homopolymer and / or a copolymer of ethylene and an olefin other than ethylene that can copolymerize with ethylene (hereinafter also referred to as a "comonomer") (hereinafter also referred to as an "ethylene polymer").

[0041] The olefins copolymerizable with ethylene are not particularly limited, but specifically include, for example, α-olefins having 3 to 15 carbon atoms, cyclic olefins having 3 to 15 carbon atoms, and olefins with the formula CH2=CHR. 1 (Here, R 1 A is an aryl group having 6 to 12 carbon atoms. Examples include compounds represented by ( ) and at least one comonomer selected from the group consisting of linear, branched, or cyclic dienes having 3 to 15 carbon atoms. Among these, α-olefins having 3 to 15 carbon atoms are preferred.

[0042] The above α-olefins are not particularly limited, but examples include propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, and the like.

[0043] [Comonomer content] The polyethylene powder of this embodiment is 13 The comonomer content, as measured by 13C-NMR, is preferably 1.0 mol% or less, more preferably 0.1 mol% or less, and even more preferably 0 mol%. When the comonomer content of the polyethylene powder of this embodiment is within the above range, decomposition tends to be suppressed, and the strength of the molded article obtained by molding the polyethylene powder tends to improve.

[0044] [Method for observing spherulites] There are no particular limitations on the method for observing the spherulite structure of polyethylene according to the present invention, but it is preferable to use an optical microscope equipped with an observation stage capable of raising the temperature to a level above the melting point of polyethylene. The polyethylene powder to be observed is preferably formed into a sheet about 1 mm thick using a compression molding machine that has been heated to a level above the melting point of polyethylene, and then the portion cut out with a razor blade or the like from a cross-section that has not been subjected to contact surface history during molding is preferably observed. Furthermore, it is preferable to sandwich the portion cut out with a razor blade or the like between a slide glass and a cover glass, and heat it again to a level above the melting point of polyethylene to make the polyethylene and the glass surface adhere tightly, thereby creating a glass slide. The magnification of the optical microscope when observing the sample can be arbitrarily selected to facilitate the analysis of the captured image. The observation position of the sample can be arbitrarily selected to facilitate the analysis of the captured image, but it is preferable to select a part that does not have air bubbles or surface irregularities in the field of view.

[0045] [Titanium content / Magnesium content / Silica content] In this embodiment, the polyethylene powder preferably has a titanium (Ti) content of less than 3 ppm by weight of polyethylene. Furthermore, the magnesium (Mg) content is preferably 10 ppm or more and less than 200 ppm. Additionally, the silica (Si) content is preferably less than 10 ppm. By adjusting the Ti, Mg, and Si content to these ranges, for example, catalyst residue can be uniformly dispersed within the polyethylene particles. Generally, a high amount of metal derived from catalyst residue remaining in the polyethylene powder tends to cause uneven thickness in the molded article. In this embodiment, the Ti, Mg, and Si content can be measured by the method described in the examples below.

[0046] The method for adjusting the titanium content, magnesium content, and silica content to the above ranges is not particularly limited, but one example is to adjust them by changing the composition of the catalyst used in the polymerization of polyethylene.

[0047] [catalyst] The polyethylene powder of the present invention can be produced by polymerizing ethylene monomers, etc., using the following catalyst. In the present invention, the catalyst for polymerizing the polyethylene powder is not particularly limited, but for example, it is composed of [A] inorganic solid particles, [B] a transition metal compound component, [C] an activator, and [D] a liquid component.

[0048] In the present invention, [A] Examples of inorganic solid particles include porous polymer materials (wherein the matrix includes, for example, polyolefins and their modified products such as polyethylene, polypropylene, polystyrene, ethylene-propylene copolymer, ethylene-vinyl ester copolymer, styrene-divinylbenzene copolymer, and partial or complete saponified ethylene-vinyl ester copolymers, as well as thermoplastic resins such as polyamide, polycarbonate, and polyester, and thermosetting resins such as phenolic resin, epoxy resin, urea resin, and melamine resin), and inorganic solid oxides of elements belonging to groups 2 to 4, 13, or 14 of the periodic table (for example, silica, alumina, magnesia, magnesium chloride, zirconia, titania, boron oxide, calcium oxide, zinc oxide, barium oxide, vanadium pentoxide, chromium oxide, thorium oxide, or mixtures thereof or composite oxides thereof). Examples of silica-containing composite oxides include silica-magnesia and silica-alumina, which are composite oxides of silica and an oxide of an element selected from elements belonging to group 2 or group 13 of the periodic table. In the present invention, it is preferable to select from silica, alumina, and composite oxides of silica and an element selected from Group 2 or Group 13 of the periodic table.

[0049] [A] There are no particular restrictions on the shape of the silica product used as inorganic solid particles; silica may be in any form, such as granular, spherical, aggregated, or fumean. Preferred examples of commercially available silica products include SD3216.30, SP-9-10046, Davison Syloid™ 245, Davison 948 or Davison 952 [all manufactured by Grace Davison Company (a subsidiary of WR Davison Company (USA))], Aerosil 812 [manufactured by Dexa AG (Germany)], ES70X [manufactured by Crossfield Corporation (USA)], P-6, P-10, Q-6 [manufactured by Fuji Silicia Co., Ltd. (Japan)], etc.

[0050] Examples of preferred organomagnesium compounds for the inorganic solid particles [A] used in the present invention include the compound represented by the following formula (4). MgR n X 2-n Formula (4) (In formula 4, R independently represents a linear, branched, or cyclic alkyl group having 1 to 12 carbon atoms or an aryl group having 6 to 20 carbon atoms; X independently represents a halide, hydride, or alkoxide group having 1 to 10 carbon atoms; and n is 1 or 2.) The compounds represented by formula (4) above may be used individually or in combination.

[0051] Examples of group R in formula (4) include methyl group, ethyl group, n-propyl group, isopropyl group, n-butyl group, isobutyl group, sec-butyl group, tert-butyl group, pentyl group, hexyl group, octyl group, decyl group, phenyl group, tolyl group, etc. Examples of group X in formula (4) include methoxy group, ethoxy group, butoxy group, hydrogen atom, chlorine atom, etc.

[0052] Next, the [B] transition metal compound components used in the present invention will be described. An example of the [B] transition metal compound components used in the present invention is the compound represented by the following formula (5). L j W k MX pX' q Equation (5) (In formula 5, L independently represents an η-bonded cyclic anionic ligand selected from the group consisting of a cyclopentadienyl group, an indenyl group, a tetrahydroindenyl group, a fluorenyl group, a tetrahydrofluorenyl group, and an octahydrofluorenyl group, wherein the ligand may have 1 to 8 substituents, each substituent independently representing a C1-C20 hydrocarbon group, a halogen atom, a C1-C12 halogen-substituted hydrocarbon group, a C1-C12 aminohydrocarbyl group, a C1-C12 hydrocarbyloxy group, or a C1-C12 dihydrocarbyl group) A substituent having up to 20 non-hydrogen atoms, selected from the group consisting of a mino group, a C1-C12 hydrocarbylphosphono group, a silyl group, an aminosilyl group, a C1-C12 hydrocarbyloxysilyl group, and a halosilyl group; M is a transition metal selected from the group of transition metals belonging to Group 4 of the periodic table with a formal oxidation state of +2, +3, or +4, and is η5-bonded to at least one ligand L; W is a divalent substituent having up to 50 non-hydrogen atoms, bonded to L and M with a valency of 1 each, thereby cooperating with L and M to form a meta The following describes a divalent substituent forming a locycle: X independently represents an anionic σ-bond ligand having up to 60 non-hydrogen atoms, selected from the group consisting of a monovalent anionic σ-bond ligand, a divalent anionic σ-bond ligand bonded to M, and a divalent anionic σ-bond ligand bonded to L and M with a 1-valent valency each; X' independently represents a neutral Lewis base coordinating compound having up to 40 non-hydrogen atoms; j is 1 or 2, however, when j is 2, possibly two ligands L having up to 20 non-hydrogen atoms. The two groups are bonded to each other via a valency group, and the divalent group is selected from the group consisting of a C1-C20 hydrocarbadiyl group, a C1-C12 halohydrocarbadiyl group, a C1-C12 hydrocarbyleneoxy group, a C1-C12 hydrocarbyleneamino group, a silanediyl group, a halosilanediyl group, and a silyleneamino group, where k is 0 or 1, and p is 0, 1, or 2, provided that if X is a monovalent anionic σ-bonded ligand, or a divalent anionic σ-bonded ligand bonded to L and M, then p is an integer at least 1 less than the formal oxidation number of M.Furthermore, if X is a divalent anionic σ-bond ligand bonded only to M, then p is an integer less than or equal to (j+1) the formal oxidation number of M, and q is 0, 1, or 2.

[0053] Examples of ligand X in the compound of formula (5) above include hydrides, halides, hydrocarbon groups having 1 to 60 carbon atoms, hydrocarbyl oxy groups having 1 to 60 carbon atoms, hydrocarbyl amide groups having 1 to 60 carbon atoms, hydrocarbyl phosphide groups having 1 to 60 carbon atoms, hydrocarbyl sulfides having 1 to 60 carbon atoms, silyl groups, and complex groups thereof.

[0054] Examples of neutral Lewis base coordinating compound X' in the compound of formula (5) above include phosphines, ethers, amines, olefins having 2 to 40 carbon atoms, dienes having 1 to 40 carbon atoms, and divalent groups derived from these compounds.

[0055] Examples of [B] transition metal compound components used in the present invention include the compound represented by the following formula (6). Formula (6) [ka] (In the formula, R 1 and R 4 Each is independently an aliphatic hydrocarbon group having 1 to 20 carbon atoms or an aromatic group having a hydrocarbon group on a ring with a total of 7 to 20 carbon atoms, R 2 and R 3 Each independently represents a hydrogen atom or a hydrocarbon group having 1 to 20 carbon atoms, and R 2 and R 3 The compounds represented by (1) may be bonded to each other to form a ring, and X and Y are each independently a halogen atom or a hydrocarbon group having 1 to 20 carbon atoms, and M is nickel or palladium.

[0056] In the above general formula (6), R 1 and R 4Examples of aliphatic hydrocarbon groups having 1 to 20 carbon atoms include linear or branched alkyl groups having 1 to 20 carbon atoms or cycloalkyl groups having 3 to 20 carbon atoms, specifically including methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, pentyl, hexyl, octyl, decyl, tetradecyl, hexadecyl, octadecyl, cyclopentyl, cyclohexyl, and cyclooctyl groups. A suitable substitution, such as a lower alkyl group, may be introduced on the ring of the cycloalkyl group.

[0057] Furthermore, examples of aromatic groups having a hydrocarbon group on a ring with a total of 7 to 20 carbon atoms include groups in which one or more linear, branched, or cyclic alkyl groups with 1 to 10 carbon atoms are introduced on an aromatic ring such as a phenyl group or a naphthyl group. 1 and R 4 As such, aromatic groups having a hydrocarbon group on the ring are preferred, and the 2,6-diisopropylphenyl group is particularly preferred. 1 and R 4 They may be identical or different to one another.

[0058] Also, R 2 and R 3 Examples of hydrocarbon groups having 1 to 20 carbon atoms include linear or branched alkyl groups having 1 to 20 carbon atoms, cycloalkyl groups having 3 to 20 carbon atoms, aryl groups having 6 to 20 carbon atoms, and aralkyl groups having 7 to 20 carbon atoms. Here, as for linear or branched alkyl groups having 1 to 20 carbon atoms and cycloalkyl groups having 3 to 20 carbon atoms, the R 1 and R 4 The same examples given in the description of aliphatic hydrocarbon groups with 1 to 20 carbon atoms can be cited. Examples of aryl groups with 6 to 20 carbon atoms include phenyl, tolyl, xylyl, naphthyl, and methylnaphthyl groups, while examples of aralkyl groups with 7 to 20 carbon atoms include benzyl and phenethyl groups.

[0059] This R 2and R 3 These may be identical or different. They may also be bonded together to form a ring. On the other hand, X and Y may be halogen atoms such as chlorine, bromine, or iodine atoms, and as a hydrocarbon group having 1 to 20 carbon atoms, the above R 2 and R 3 The hydrocarbon groups having 1 to 20 carbon atoms in the formula are as described above. Chlorine atoms or methyl groups are particularly preferred for X and Y. Furthermore, X and Y may be the same or different from each other.

[0060] Specific examples of the [B] transition metal compound component used in the present invention include the following compounds. Bis(cyclopentadienyl)methylzirconium hydride, bis(cyclopentadienyl)ethylzirconium hydride, bis(cyclopentadienyl)phenylzirconium hydride, bis(cyclopentadienyl)benzylzirconium hydride, bis(cyclopentadienyl)neopentylzirconium hydride, bis(methylcyclopentadienyl)zirconium dimethyl, bis(n-butylcyclopentadienyl)zirconium dimethyl, bis(indenyl)zirconium dimethyl, (pentamethylcyclopentadienyl)(cyclopentadienyl)zirconium dimethyl, bis(cyclopentadienyl)zirconium dimethyl, bis(pentamethylcyclopentadienyl)zirconium dimethyl, bis(cyclopentadienyl)zirconium diphenyl, bis(cyclopentadienyl)zirconium dibenzyl, bis(cyclopentadienyl) Zirconium dihydride, bis(fluorenyl)zirconium dimethyl, ethylenebis(indenyl)zirconium dimethyl, ethylenebis(indenyl)zirconium diethyl, ethylenebis(indenyl)zirconium dihydride, ethylenebis(4,5,6,7-tetrahydro-1-indenyl)zirconium dimethyl, ethylenebis(4-methyl-1-indenyl)zirconium dimethyl, ethylenebis(5-methyl-1-indenyl)zirconium dimethyl, ethylenebis(6-methyl-1-indenyl)zirconium dimethyl, ethylenebis(7-methyl-1-indenyl)zirconium dimethyl, ethylenebis(5-methoxy-1-indenyl)zirconium dimethyl, ethylenebis(2,3-dimethyl-1-indenyl)zirconium dimethyl, ethylenebis(4,7-dimethyl-1-indenyl)dimethylzirconium, ethylenebis-(4,7-Dimethoxy-1-indenyl)zirconium dimethyl, methylenebis(cyclopentadienyl)zirconium dihydride, methylenebis(cyclopentadienyl)zirconium dimethyl, isopropylidene(cyclopentadienyl)zirconium dihydride, isopropylidene(cyclopentadienyl)zirconium dimethyl, isopropylidene(cyclopentadienyl-fluorenyl)zirconium dihydride, isopropylidene(cyclopentadienyl-fluorenyl)zirconium dihydride Titanium dimethyl, silylene bis(cyclopentadienyl) zirconium dihydride, silylene bis(cyclopentadienyl) zirconium dimethyl, dimethylsilylene(cyclopentadienyl) zirconium dihydride, dimethylsilylene(cyclopentadienyl) zirconium dimethyl, [(Nt-butylamide)(tetramethyl-η5-cyclopentadienyl)-1,2-ethanediyl]titanium dimethyl, [(Nt-butylamide)(tetramethyl-η5-cyclopentadienyl) di [methylsilane]titaniumdimethyl, [(N-methylamide)(tetramethyl-η5-cyclopentadienyl)dimethylsilane]titaniumdimethyl, [(N-phenylamide)(tetramethyl-η5-cyclopentadienyl)dimethylsilane]titaniumdimethyl, [(N-benzylamide)(tetramethyl-η5-cyclopentadienyl)dimethylsilane]titaniumdimethyl, [(Nt-butylamide)(η5-cyclopentadienyl)-1,2-ethanediyl]titaniumdimethyl [(Nt-butylamide)(η5-cyclopentadienyl)dimethylsilane]titaniumdimethyl, [(N-methylamide)(η5-cyclopentadienyl)-1,2-ethanediyl]titaniumdimethyl, [(N-methylamide)(η5-cyclopentadienyl)dimethylsilane]titaniumdimethyl, [(Nt-butylamide)(η5-indenyl)dimethylsilane]titaniumdimethyl, [(N-benzylamide)(η5-indenyl)dimethylsilane]titaniumdimethyl, etc.

[0061] Specific examples of the [B] transition metal compound component used in the present invention include compounds whose names can be obtained by replacing the "dimethyl" part of the names of each zirconium and titanium compound listed above as specific examples of the [B] transition metal compound component (this is the part at the end of the name of each compound, that is, immediately after the "zirconium" or "titanium" part, and is the name corresponding to the X″ part in formula (7) above) with any of the following: "dibenzyl", "2-(N,N-dimethylamino)benzyl", "2-butene-1,4-diyl", "s-trans-η4-1,4-diphenyl-1,3-butadiene", "s-trans-η4-3-methyl-1,3-pentadiene", "s-trans-η4-1,4- Dibenzyl-1,3-butadiene, s-trans-η4-2,4-hexadiene, s-trans-η4-1,3-pentadiene, s-trans-η4-1,4-ditril-1,3-butadiene, s-trans-η4-1,4-bis(trimethylsilyl)-1,3-butadiene, s-cis-η4-1,4-diphenyl-1,3-butadiene, "s-cis-η4-3-methyl-1,3-pentadiene", "s-cis-η4-1,4-dibenzyl-1,3-butadiene", "s-cis-η4-2,4-hexadiene", "s-cis-η4-1,3-pentadiene", "s-cis-η4-1,4-ditril-1,3-butadiene", "s-cis-η4-1,4-bis(trimethylsilyl)-1,3-butadiene", etc.

[0062] The [B] transition metal compound components used in the present invention can be synthesized by generally known methods. An example of a preferred synthesis method for the transition metal compounds used as [B] transition metal compound components in the present invention is the method disclosed in U.S. Patent No. 5,491,246. These [B] transition metal compound components may be used individually or in combination in the present invention.

[0063] The [C]activators used in the present invention will now be described. Examples of [C]activators include compounds defined by the following general formula (7). [LH]d+ [M m Q p ] d- Formula (7) However, in the formula [LH] d+ L is a proton-donating Brønsted acid, and L is a neutral Lewis base. Also, in the formula [M m Q p ] d- is a miscible non-coordinating anion, M is a metal or metalloid selected from groups 5 through 15 of the periodic table, Q is independently a hydride, dialkylamide group, halide, alkoxide group, alluroxide group, hydrocarbon group, or substituted hydrocarbon group with up to 20 carbon atoms, and there is one or fewer halides in Q. Also, m is an integer from 1 to 7, p is an integer from 2 to 14, d is an integer from 1 to 7, and pm = d.

[0064] In the present invention, a preferred example of the [C] activator is represented by the following general formula (C-1). [M m Q n (G q (TH) r ) z ] d- (C-1) However, M is a metal or metalloid selected from groups 5 through 15 of the periodic table. Q is as defined in general formula (8), G is a polyvalent hydrocarbon group with a valency of r+1 that bonds with boron and T, T is O, S, NR, or PR, where R is hydrocarbyl, trihydrocarbylsilyl, trihydrocarbylgermanium, or hydrogen. Also, m is an integer from 1 to 7, n is an integer from 0 to 7, q is an integer of 0 or 1, r is an integer from 0 to 3, z is an integer from 1 to 8, d is an integer from 1 to 7, and n + zm = d.

[0065] A more preferred example of component (C-1) of the present invention is represented by the following general formula (C-2). [LH] + [BQ3Q'] - (C-2) However, in the formula [LH] +is a proton-donating Brønsted acid, and L is a neutral Lewis base. Also, in the formula [BQ3Q'] - Q is a compatible, non-coordinating anion, Q is a pentafluorophenyl group, and the remaining Q' is a substituted aryl group having 6 to 20 carbon atoms and one OH group as a substituent.

[0066] Specific examples of the compatible non-coordinating anions of the present invention include, for example, tetrakisphenylborate, tri(p-tolyl)(phenyl)borate, tris(pentafluorophenyl)(phenyl)borate, tris(2,4-dimethylphenyl)(hydrophenyl)borate, tris(3,5-dimethylphenyl)(phenyl)borate, tris(3,5-di-trifluoromethylphenyl)(phenyl)borate, tris(pentafluorophenyl)(cyclohexyl)borate, tris(pentafluorophenyl)(naphthyl)borate, tetrakis(pentafluorophenyl)borate, triphenyl(hydroxyphenyl)borate, diphenyl-di(hydroxyphenyl)borate, triphenyl(2,4-dihydroxyphenyl)borate, tri(p-tolyl)(hydroxyphenyl)borate, and tris(penta Examples include tris(2,4-hydroxyphenyl)(hydroxyphenyl)borate, tris(3,5-dimethylphenyl)(hydroxyphenyl)borate, tris(3,5-di-trifluoromethylphenyl)(hydroxyphenyl)borate, tris(pentafluorophenyl)(2-hydroxyethyl)borate, tris(pentafluorophenyl)(4-hydroxybutyl)borate, tris(pentafluorophenyl)(4-hydroxycyclohexyl)borate, tris(pentafluorophenyl)(4-(4'-hydroxyphenyl)phenyl)borate, tris(pentafluorophenyl)(6-hydroxy-2-naphthyl)borate, and the most preferred is tris(pentafluorophenyl)(4-hydroxyphenyl)borate.

[0067] [C] The activator may be a reaction product with an organoaluminum compound. Examples of organoaluminum compounds include trimethylaluminum, triethylaluminum, tributylaluminum, trihexylaluminum, trioctylaluminum, tridecylaluminum, etc., or reaction products of these alkylaluminums with alcohols such as methyl alcohol, ethyl alcohol, butyl alcohol, pentyl alcohol, hexyl alcohol, octyl alcohol, decyl alcohol, etc., such as dimethylmethoxyaluminum, diethylethoxyaluminum, dibutylbutoxyaluminum, etc. Furthermore, the reaction products with the above organoaluminum compounds may be used individually or in combination.

[0068] Next, the liquid component [D] used in the present invention will be described. Examples of the liquid component [D] used in the present invention include the compound defined by the following general formula (8). [-Al(Me)-O-] n -[-Al(R)-O-] m Formula (8) In formula 8, R is a hydrogenated carbide group having 1 to 12 carbon atoms. Specifically, examples of R in the above formula include a methyl group, ethyl group, n-propyl group, isopropyl group, n-butyl group, isobutyl group, pentyl group, hexyl group, octyl group, decyl group, cyclohexyl group, and cyclooctyl group. Among these, the methyl group and ethyl group are preferred, and the methyl group is particularly preferred. In the above formula, for example, examples of organoaluminum oxy compounds composed of one type of alkylaluminum unit include methylaluminoxane, ethylaluminoxane, n-propylaluminoxane, isopropylaluminoxane, n-butylaluminoxane, isobutylaluminoxane, pentylaluminoxane, hexylaluminoxane, octylaluminoxane, decylaluminoxane, cyclohexylaluminoxane, and cyclooctylaluminoxane. Among these, methylaluminoxane and ethylaluminoxane are preferred, and methylaluminoxane is particularly preferred. As described above, the organoaluminum oxy compounds of the present invention are composed of alkyloxyaluminum units represented by the above formula, but are not necessarily limited to compounds consisting of one type of constituent unit, and may consist of multiple types of constituent units. For example, methylethylaluminoxane, methylpropylaluminoxane, methylbutylaluminoxane, etc., and the ratio of each constituent unit can be arbitrarily taken in the range of 0 to 100%. Furthermore, it may be a mixture of multiple types of organoaluminum oxy compounds consisting of one type of constituent unit. For example, a mixture of methylaluminoxane and ethylaluminoxane, a mixture of methylaluminoxane and n-propylaluminoxane, a mixture of methylaluminoxane and isobutylaluminoxane, etc. Also, n and m can be any numbers, but from the viewpoint of ease of manufacture, the ratio of m to n m / n is preferably 0.1 or more and 10 or less, and more preferably 0.3 or more and 5 or less.

[0069] Furthermore, the organoaluminum oxy compounds of the present invention may contain unreacted chemical substances resulting from their manufacturing process. In other words, organoaluminum oxy compounds are generally obtained by the reaction of trialkylaluminum and H2O, but some of these raw materials may remain as unreacted chemical substances. For example, in the synthesis of methylalkoxane, trimethylaluminum and H2O are used as raw materials, and one or both of these raw materials may be contained in the methylalkoxane as unreacted chemical substances. In the above example of a method for producing organoaluminum oxy compounds, trialkylaluminum is usually used in greater quantities than H2O, so trialkylaluminum is often included in the organoaluminum oxy compound as a residual chemical substance.

[0070] Next, a method for producing a polyethylene polymerization catalyst from [A] inorganic solid particles, [B] transition metal compound components, [C] activators, and [D] liquid components will be described.

[0071] In this invention, a polyethylene polymerization catalyst is produced by simultaneously adding [B] a transition metal compound component and [C] an activator in the presence of [A] inorganic solid particles and [D] a liquid component. More specifically, a solid catalyst for olefin polymerization is produced by adding an inert reaction solvent to a reactor that has been sufficiently purged with nitrogen, adding [A] inorganic solid particles and [D] liquid components to form a slurry, and then adding [B] transition metal compound components and [C] activator separately and simultaneously to the reactor. This means that in the presence of [A] inorganic solid particles, equal amounts of [B] transition metal compound components and [C] activator react and are supported. The inert reaction solvent in this invention includes aliphatic hydrocarbons such as hexane and heptane, and aromatic hydrocarbons such as benzene and toluene, but linear or branched hydrocarbon compounds such as isobutane, pentane, isopentane, hexane, heptane, octane, decane, dodecane, and kerosene are preferably used.

[0072] In the present invention, there are no particular restrictions on the amount or ratio of each component used, but it is preferable to use a sufficient amount of [C] activator to activate the [B] transition metal compound component. In the present invention, the [B] transition metal compound component is preferably 5 × 10 per 1 g of [A] inorganic solid particles. -6 ~10 -2 Mole, Comfortable 10 -5 ~10 -3 It is used in terms of moles.

[0073] In the present invention, a liquid component [E] may be used as an impurity scavenger. Liquid component [E] is a hydrocarbon solvent-soluble organomagnesium compound synthesized by the reaction of an organomagnesium compound [E-1] soluble in a hydrocarbon solvent represented by the following formula (6) with a compound [E-2] selected from amines, alcohols, and siloxane compounds.

[0074] (M 2 ) a (Mg) b (R 3 ) c (R 4 ) d Formula (9) [In formula 9, M 2 R is a metal atom belonging to groups 1, 2, 12, and 13 of the periodic table. 3 and R 4 is a hydrocarbon group having 2 to 20 carbon atoms, and a, b, c, and d are real numbers satisfying the following relationship: 0 ≤ a, 0<b、0≦c、0≦d、c+d> 0, e × a + 2b = c + d (where e is M) 2 (Valence of atoms)

[0075] In the present invention, there are no particular restrictions on the reaction between the organomagnesium compound [E-1] and compound [E-2], but it is preferable to carry out the reaction in an inert reaction medium such as an aliphatic hydrocarbon such as hexane or heptane, or an aromatic hydrocarbon such as benzene or toluene, at a temperature between room temperature and 150°C. There are no particular restrictions on the order of this reaction, and any of the following methods are preferred: adding compound [E-2] to the organomagnesium compound [E-1], adding the organomagnesium compound [E-1] to compound [E-2], or adding both simultaneously. There are no particular restrictions on the reaction ratio between the organomagnesium compound [E-1] and compound [E-2], but the molar ratio of compound [E-2] to the total metal atoms contained in the liquid component [E] synthesized by the reaction is preferably 0.01 to 2, and more preferably 0.1 to 1.

[0076] In this invention, liquid component [E] may be used alone or as a mixture of two or more components. This liquid component [E] does not significantly reduce polymerization activity even at high concentrations, and therefore can exhibit high polymerization activity over a wide concentration range. For this reason, polyethylene polymerization catalysts containing liquid component [E] allow for easy control of polymerization activity. There are no particular restrictions on the concentration of the liquid component [E] used in polymerization, but it is preferable that the molar concentration of all metal atoms contained in the liquid component [E] is 0.001 mmol / liter or more and 10 mmol / liter or less, and more preferably 0.01 mmol / liter or more and 5 mmol / liter or less. A concentration of 0.001 mmol / liter or more is preferable in order to avoid the problem that the scavenger effect on impurities may not be sufficient, and a concentration of 10 mmol / liter or less is preferable in order to avoid the problem that the polymerization activity may decrease.

[0077] Next, we will discuss organomagnesium compounds [E-1]. The organomagnesium compound [E-1] is represented by formula (9) above. Note that in formula (9) above, it is shown as a complex compound of organomagnesium soluble in hydrocarbon solvents, but (R3 This includes 2Mg and all complexes of these with other metal compounds. The relationship between symbols a, b, c, and d, e×a+2b=c+d, shows the stoichiometry between the valence of a metal atom and its substituent.

[0078] In the above formula, R 3 R 4 The hydrocarbon group represented is an alkyl group, a cycloalkyl group, or an aryl group, and is preferably a methyl group, an ethyl group, a propyl group, a 1-methylethyl group, a butyl group, a 1-methylpropyl group, a 2-methylpropyl group, a 1,1-dimethylethyl group, a pentyl group, a hexyl group, an octyl group, a decyl group, a phenyl group, or a tolyl group, more preferably an alkyl group, and even more preferably a primary alkyl group.

[0079] If a > 0, then metal atom M 2 As such, metallic elements belonging to the groups 1, 2, 12, and 13 of the periodic table can be used, such as lithium, sodium, potassium, beryllium, zinc, boron, and aluminum, but aluminum, boron, beryllium, and zinc are particularly preferred.

[0080] metal atom M 2 There are no particular restrictions on the molar ratio of magnesium to a b / a, but a range of 0.1 to 50 is preferred, and a range of 0.5 to 10 is more preferred. Also, when a=0, it is preferable that the organomagnesium compound [E-1] is an organomagnesium compound soluble in a hydrocarbon solvent, and R in formula (9) above 3 , R 4 It is even more preferable that it is one of the following three groups (9-1), (9-2), and (9-3).

[0081] (9-1):R 3 , R 4 At least one of them is a secondary or tertiary alkyl group having 4 to 6 carbon atoms, preferably R 3 , R 4Both have 4 to 6 carbon atoms, and at least one of them is a secondary or tertiary alkyl group. (9-2): R 3 and R 4 are alkyl groups with different numbers of carbon atoms, preferably R 3 is an alkyl group with 2 or 3 carbon atoms, and R 4 is an alkyl group with 4 or more carbon atoms. (9-3): R 3 and R 4 at least one of them is a hydrocarbon group with 6 or more carbon atoms, preferably R 3 and R 4 are both alkyl groups with 6 or more carbon atoms.

[0082] The following specifically show these groups. In (9-1), examples of the secondary or tertiary alkyl group having 4 to 6 carbon atoms include 1-methylpropyl group, 1,1-dimethylethyl group, 1-methylbutyl group, 1-ethylpropyl group, 1,1-dimethylpropyl group, 1-methylpentyl group, 1-ethylbutyl group, 1,1-dimethylbutyl group, 1-methyl-1-ethylpropyl group, etc., and the 1-methylpropyl group is particularly preferred. In (9-2), examples of the alkyl group having 2 or 3 carbon atoms include ethyl group and propyl group, and the ethyl group is particularly preferred. Examples of the alkyl group having 4 or more carbon atoms include butyl group, amyl group, hexyl group, octyl group, etc., and the butyl group and hexyl group are particularly preferred. In (9-3), examples of the alkyl group having 6 or more carbon atoms include hexyl group, octyl group, decyl group, phenyl group, etc., and an alkyl group is preferred, and the hexyl group is particularly preferred.

[0083] Generally, increasing the number of carbon atoms of the alkyl group makes it easier to dissolve in the hydrocarbon solvent, but the viscosity of the solution tends to increase, and it is not preferable in terms of handling to use an alkyl group with an overly long chain. The above-mentioned organomagnesium compound is used as a hydrocarbon solution, and it can be used without problem even if a trace amount of complexing agents such as ether, ester, and amine is contained or remains in the solution.

[0084] Next, we will discuss compound [E-2]. This compound belongs to the group consisting of amines, alcohols, and siloxane compounds. In the present invention, there are no particular restrictions on the amine compound, but aliphatic, alicyclic, or aromatic amines are preferred. Specifically, examples include methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, butylamine, dibutylamine, tributylamine, hexylamine, dihexylamine, trihexylamine, octylamine, dioctylamine, trioctylamine, aniline, N-methylaniline, N,N-dimethylaniline, toluidine, and the like.

[0085] In the present invention, there are no particular restrictions on the alcohol compound, but methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, 1,1-dimethylethanol, pentanol, hexanol, 2-methylpentanol, 2-ethyl-1-butanol, 2-ethyl-1-pentanol, 2-ethyl-1-hexanol, 2-ethyl-4-methyl-1-pentanol, 2-propyl-1-heptanol, 2-ethyl-5-methyl-1-octanol, 1-octanol, 1-decanol, cyclohexanol, and phenol are preferred, and 1-butanol, 2-butanol, 2-methyl-1-pentanol, and 2-ethyl-1-hexanol are more preferred.

[0086] In the present invention, there are no particular restrictions on the siloxane compound, but a siloxane compound having a structural unit represented by the following formula (10) is preferred. [ka] (In the above equation (10), R 11 and R 12 (This group is selected from the group consisting of hydrogen, hydrocarbon groups having 1 to 30 carbon atoms, and substituted hydrocarbon groups having 1 to 40 carbon atoms.)

[0087] In the present invention, there are no particular restrictions on the hydrocarbon group, but methyl, ethyl, propyl, 1-methylethyl, butyl, 1-methylpropyl, 2-methylpropyl, 1,1-dimethylethyl, pentyl, hexyl, octyl, decyl, phenyl, tolyl, and vinyl groups are preferred. Furthermore, there are no particular restrictions on the substituted hydrocarbon group, but trifluoropropyl is preferred.

[0088] In the present invention, the siloxane compound can be used in the form of a chain or cyclic compound consisting of one or more constituent units, such as a dimer or more.

[0089] In the present invention, preferred siloxane compounds include symmetric dihydrotetramethyldisiloxane, hexamethyldisiloxane, hexamethyltrisiloxane, pentamethyltrihydrotrisiloxane, cyclic methylhydrotetrasiloxane, cyclic methylhydropentasiloxane, cyclic dimethyltetrasiloxane, cyclic methyltrifluoropropyltetrasiloxane, cyclic methylphenyltetrasiloxane, cyclic diphenyltetrasiloxane, (terminally methyl-sealed)methylhydropolysiloxane, dimethylpolysiloxane, (terminally methyl-sealed)phenylhydropolysiloxane, and methylphenylpolysiloxane.

[0090] In addition, in the present invention, the catalyst for olefin polymerization may include other components useful for olefin polymerization in addition to the components described above.

[0091] Next, the method for producing polyethylene powder according to the present invention will be described.

[0092] The polyethylene powder of the present invention is obtained by homopolymerizing ethylene using the olefin polymerization catalyst of the present invention, or by polymerization of ethylene with α-olefins, preferably those having 3 to 20 carbon atoms, cyclic olefins, or those with the general formula CH2=CHR. 13 (However, R 13is an aryl group having 6 to 20 carbon atoms. A compound represented by the formula ( ) can be copolymerized with at least one olefin selected from the group consisting of linear, branched or cyclic dienes having 4 to 20 carbon atoms.

[0093] In the present invention, the α-olefins having 3 to 20 carbon atoms are, for example, propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene. The cyclic olefins having 3 to 20 carbon atoms are, for example, cyclopentene, cyclohexene, cycloheptene, norbornene, 5-methyl-2-norbornene, tetracyclododecene, and 2-methyl-1,4,5,8-dimethano-1,2,3,4,4a,5,8,8a-octahydronaphthalene. The general formula CH2=CHR 13 (where R 13 is an aryl group having 6 to 20 carbon atoms.) Examples of the compound represented by the formula include styrene and vinylcyclohexane. Examples of the linear, branched or cyclic dienes having 4 to 20 carbon atoms include 1,3-butadiene, 1,4-pentadiene, 1,5-hexadiene, 1,4-hexadiene, and cyclohexadiene.

[0094] The density and physical properties of the ethylene polymer can be controlled by copolymerization of ethylene with the above-mentioned olefin (comonomer). The polymerization of olefins according to the present invention can be carried out by either suspension polymerization or gas-phase polymerization. In suspension polymerization, an inert hydrocarbon solvent can be used as the medium for suspension polymerization, and the olefin itself can also be used as the solvent. There are no particular restrictions on the inert hydrocarbon solvent, but aliphatic hydrocarbons such as propane, butane, 2-methylpropane, pentane, hexane, heptane, octane, decane, dodecane, and kerosene; alicyclic hydrocarbons such as cyclopentane, cyclohexane, and methylcyclopentane; aromatic hydrocarbons such as benzene, toluene, and xylene; and halogenated hydrocarbons such as ethyl chloride, chlorobenzene, and dichloromethane are preferred, with propane, butane, 2-methylpropane, pentane, hexane, and heptane being particularly preferred. Furthermore, two or more types of inert hydrocarbon solvents can be mixed and used.

[0095] There are no particular limitations on the method of adding the olefin polymerization catalyst of the present invention to the polymerizer, but it is preferable to add it to the polymerizer as a slurry of the above-mentioned inert hydrocarbon solvent, and butane, 2-methylpropane, pentane, hexane, and heptane are more preferable.

[0096] In the present invention, there are no particular restrictions on the amount of catalyst added in the polymerization of olefins, but it is preferable to adjust the catalyst concentration in the polymerizer so that the weight of the catalyst relative to the weight of the polymer obtained per hour is 0.001 wt% or more and 1 wt% or less. There are no particular restrictions on the polymerization temperature, but it is preferably 0°C or higher, more preferably 50°C or higher, even more preferably 60°C or higher, and preferably 150°C or lower, more preferably 110°C or lower, and even more preferably 100°C or lower. There are no particular restrictions on the polymerization pressure, but it is preferably 0.1 MPa or more and 10 MPa or lower, even more preferably 0.2 MPa or more and 5 MPa or higher and even more preferably 0.5 MPa or more and 3 MPa or lower. There are no particular restrictions on the form of this polymerization reaction, and batch, semi-continuous, or continuous methods are all preferable. It is also possible to carry out polymerization in two or more stages with different reaction conditions.

[0097] The molecular weight of the olefin polymer obtained in this invention can also be adjusted by changing the hydrogen concentration in the polymerizer or the polymerization temperature, as described in publication DE3127133.2 and other documents.

[0098] [Molded body] Next, a method for obtaining a molded article in the present invention will be described. The polyethylene powder of this embodiment can be molded by various methods. The molded article of this embodiment is obtained by molding the polyethylene powder described above. The molded article of this embodiment is not particularly limited, but can be obtained by known methods such as injection molding, extrusion molding, or stretch molding, and can be used for various applications. Specific examples of the molded article of this embodiment are not limited to, but include, for example, separators for secondary batteries (e.g., microporous membranes), fibers (e.g., high-strength fibers), and films, with lithium ion microporous membranes, high-strength fibers, and films being particularly suitable.

[0099] [Separator for secondary batteries] The method for manufacturing a separator for secondary batteries (e.g., a microporous membrane) is not particularly limited, but for example, a wet process using a solvent is used, in which the material is extruded, stretched, extracted, and dried using an extruder equipped with a T-die. Specifically, although not particularly limited, the following manufacturing methods are examples.

[0100] High molecular weight polyethylene powder and liquid paraffin are blended with additives such as antioxidants as needed, and the melting point of the polyethylene powder (T m2 A slurry-like liquid is prepared by stirring at a temperature 30°C lower than the specified temperature. The obtained slurry-like liquid is put into a kneader, kneaded at a constant temperature, then hot-pressed, and finally cooled-pressed to form a gel sheet. The thickness of the gel sheet is adjusted by using a metal frame.

[0101] This gel-like sheet is stretched using a biaxial stretching machine, and the stretched film is cut out and fixed to a metal frame. Then, it is immersed in hexane to extract and remove the liquid paraffin, and then dried. Further heat fixing can be performed to obtain a microporous film.

[0102] [fiber] The method for producing fibers (e.g., high-strength fibers) is not particularly limited, but one example is a method in which liquid paraffin and the above-mentioned polyethylene powder are kneaded and spun, and then heated and stretched. Specifically, although not particularly limited, the following method is an example: polyethylene powder and liquid paraffin are blended with additives such as antioxidants as needed, and the melting point (T) of the polyethylene powder is adjusted. m2 A slurry-like liquid is prepared by stirring at a temperature 30°C lower than the specified temperature.

[0103] Next, the slurry liquid is put into a kneader and kneaded at a constant temperature. Then, it is passed through a spinneret attached to the tip of an extruder and spun. Next, the extruded yarn containing liquid paraffin is wound up at a point away from the spinneret. Then, in order to remove the liquid paraffin from the wound yarn, the yarn is immersed in hexane for extraction and then dried. The resulting yarn is primary stretched in a constant temperature bath, and then secondary stretched in the constant temperature bath until just before the yarn breaks, thereby obtaining high-strength fibers (stretched yarn).

[0104] Next, the present invention will be described in more detail based on examples, but the present invention is not limited in any way by these examples. [Examples]

[0105] In the present invention, the ethylene and hexane used in the examples and comparative examples were dehydrated using MS-3A (manufactured by Showa Union), and the hexane was further deoxygenated by vacuum degassing using a vacuum pump before use.

[0106] [Method for producing polyethylene and method for evaluating its physical properties] Polyethylene was prepared using the methods shown in the Examples and Comparative Examples. The physical properties of the obtained polymers were evaluated using the following methods.

[0107] [Measurement of intrinsic viscosity] The intrinsic viscosity IV of polyethylene powder was measured in accordance with ISO 1628-3 (2010) as follows. Polyethylene powder was weighed in the range of 4.0 to 4.5 mg, degassed with a vacuum pump and purged with nitrogen in 20 mL of decahydronaphthalene (with 1 g / L of 2,6-di-t-butyl-4-methylphenol added; hereinafter referred to as decalin), and dissolved in a dissolution tube, which had been degassed with a vacuum pump and purged with nitrogen, by stirring at 150°C for 90 minutes to obtain the solution. A Cannon-Fenske type viscometer (manufactured by Shibata Scientific Instruments Co., Ltd.: product number -100) was used as the viscosity tube. [Measurement of molecular weight distribution] The molecular weight distribution was defined as the ratio (Mw / Mn) of the weight-average molecular weight (Mw) to the number-average molecular weight (Mn) obtained from gel permeation chromatography (GPC). GPC measurements were performed under the following conditions. Molecular weight calibration was performed at 12 points in the range of 1,050 to 20,600,000 MW (Molecular Weight) of standard polystyrene manufactured by Tosoh Corporation. The MW of each standard polystyrene was multiplied by a coefficient of 0.43 to obtain the polyethylene-equivalent molecular weight. A primary calibration line was created from the plot of elution time and polyethylene-equivalent molecular weight to determine the weight-average molecular weight (Mw), number-average molecular weight (Mn), and viscosity-average molecular weight (Mv). In addition, the proportion of molecules with a molecular weight of 1,000,000 or more relative to the total was calculated from the molecular weight distribution obtained from the GPC measurement. (Measurement conditions) Equipment: PolymerChar GPC-IR Detector: PolymerChar IR5 Column: Showa Denko Corporation UT-807 (1 piece) and Tosoh Corporation GMHHRH ( Use by connecting two S)HT units in series. Mobile phase: o-dichlorobenzene Column temperature: 140℃ Flow rate: 1.0ml / min Sample concentration: 4 mg / 8 mL

[0108] [Measurement of titanium, magnesium, and silicon content in polyethylene powder] The elemental content of polyethylene powder obtained in the examples and comparative examples was measured by high-frequency plasma mass spectrometry in accordance with JIS K0133. Sample preparation was carried out by pressurized acid decomposition with nitric acid using a microwave decomposition apparatus (model ETHOSTC, manufactured by Milestone General Co., Ltd.). The content of titanium, magnesium, and silicon as contained metallic elements in the polyethylene powder was quantified using the internal standard method with ICP-MS (inductively coupled plasma mass spectrometer, model X series X7, manufactured by Thermo Fisher Scientific).

[0109] [Measurement of the extracellular crystallization initiation temperature] Extrapolated crystallization start temperature (T ic The measurements were performed using a PerkinElmer DSC8000 differential scanning calorimeter (DSC) under the following temperature conditions. 8.3-8.5 mg of polyethylene polymer powder was weighed and placed in an aluminum sample pan. An aluminum cover was attached to this pan and placed inside the differential scanning calorimeter. Temperature calibration was performed using pure indium while purging with nitrogen at a flow rate of 20 mL / min. (Temperature conditions) 1) After holding at 50°C for 1 minute, the temperature was increased to 180°C at a heating rate of 10°C / min. 2) After being held at 180°C for 5 minutes, the temperature was lowered to 50°C at a rate of 10°C / min. 3) After holding at 50°C for 5 minutes, the temperature was increased to 180°C at a heating rate of 10°C / min. The temperature at the intersection of the straight line extending the high-temperature baseline obtained during the cooling process described in 2) above toward the low-temperature side, and the tangent line drawn from the point where the slope of the high-temperature curve of the crystallization peak is maximum, is defined as the extrapolation crystallization start temperature (T ic )

[0110] [Polyethylene spherulite observation] Polyethylene powder obtained in the examples and comparative examples was pressed into 1 mm thick test specimens using a compression molding machine (SFA-37H model, manufactured by Shinto Metal Industry Co., Ltd.). Heat molding was performed at 210°C and 5 MPa for 5 minutes, followed by 15 MPa for 25 minutes, and then cooling molding was performed at 25°C and 10 MPa for 10 minutes. The center of the obtained test specimen was cut out to 2 mm x 5 mm using a razor blade. The cut-out cross-section of the test specimen was cut to a thickness of 15 μm using a microtome and placed on a glass slide. A coverslip was placed on top to prepare the observation slide.

[0111] The prepared slide was placed in a vacuum dryer, a 160g aluminum square bar was placed on top, and the temperature was raised to 180°C while vacuum degassing was performed. After reaching 180°C, heating and vacuum degassing were performed for 1 hour. After heating and vacuum degassing was complete, the specimen was removed and cooled to room temperature to prepare a slide for spherulite observation. The slide was placed on a heat stage, and the cooling process of the measurement particles from 150°C to 100°C was observed using an optical microscope with a camera under the following heating conditions. During the cooling process, observation images of the measurement spherulites were taken every 4 seconds, and after the measurement was completed, image analysis was performed using OpenCV in Python according to the following procedure to measure the characteristic quantities of the spherulites. (Conditions for heating) (1) Heat from 30°C to 180°C at a rate of 20°C / min (2) Hold at 180°C for 5 minutes (3) Cool down from 180°C to 140°C at a rate of 20°C / min (4) Cooling from 140°C to 115°C at a rate of 2°C / min

[0112] [Image Analysis] To observe the initial stages of spherulite formation, we used Python as the programming language, OpenCV as the library, and 1200 x 1900 pixel images taken with a microscope. Specifically, we observed images obtained by DSC at a Tic temperature of +2.0°C.

[0113] The methods for obtaining Figures 1-4 as specific analysis examples are described below. First, a 1200 × 1900 pixel image (Figure 1) taken with a microscope was cropped to show only the area where spherulites were present. However, to obtain a sufficient number of spherulites to observe, the cropping area was set to 600 × 1000 pixels or larger. The resulting image is shown in Figure 2. Next, to remove contaminants other than spherulites present in the image, noise was removed using a bilateral filter. The resulting image is shown in Figure 3. Furthermore, adaptive binarization was performed to obtain the contours of the spherulites. The resulting image is shown in Figure 4. From the image in Figure 4, the characteristic quantities of the spherulites (area average, average circularity, and circularity skewness) were calculated.

[0114] The execution conditions for the bilateral filter can be arbitrarily selected, for example, as shown in the underlined part of condition (1), under conditions that an observer can observe with the naked eye and consider to be sufficient to achieve the objective of smoothing noise. These values ​​are generally expressed as kernel size, standard deviation in color space, and standard deviation in coordinate space, but this is not limited to the present invention. cv2.bilateralFilter(image, 15 , 25 , 25 Condition (1)

[0115] The conditions for performing adaptive binarization can be arbitrarily selected, for example, as shown in the underlined portion of condition (2), under conditions that an observer can observe with the naked eye and consider to be sufficient to obtain the outline of the spherulite. These values ​​are generally expressed as the brightness set when a threshold is exceeded, the kernel size used for threshold calculation, and a constant to be subtracted from the calculated threshold, but this is not limited to the present invention. cv2.adaptiveThreshold(image, 255 ,cv2.ADAPTIVE_THRESH_MEAN_C,cv2.THRESH_BINARY, 101 , 3 ) Conditional expression (2)

[0116] The methods for obtaining Figures 5-8 as specific analysis examples are described below. First, a 1200 × 1900 pixel image (Figure 5) taken with a microscope was cropped to show only the area where spherulites were present. However, to obtain a sufficient number of spherulites to observe, the cropping area was set to 600 × 1000 pixels or larger. The resulting image is shown in Figure 6. Next, to remove contaminants other than spherulites present in the image, noise was removed using a bilateral filter. The resulting image is shown in Figure 7. Furthermore, adaptive binarization was performed to obtain the contours of the spherulites. The resulting image is shown in Figure 8. From the image in Figure 8, the characteristic quantities of the spherulites (area average, average circularity, and circularity skewness) were calculated.

[0117] The execution conditions for the bilateral filter can be arbitrarily selected, for example, as shown in the underlined portion of condition (3), under conditions that an observer can observe with the naked eye and consider to be sufficient to achieve the objective of smoothing noise. These values ​​are generally expressed as kernel size, standard deviation in color space, and standard deviation in coordinate space, but this is not limited to the present invention. cv2.bilateralFilter(image, 5 , 25 , 25 ) Conditional expression (3)

[0118] The conditions for performing adaptive binarization can be arbitrarily selected, for example, as shown in the underlined portion of condition (4), under conditions that an observer can observe with the naked eye and consider to be sufficient to obtain the outline of the spherulite. These values ​​are generally expressed as the brightness set when a threshold is exceeded, the kernel size used for threshold calculation, and a constant to be subtracted from the calculated threshold, but this is not limited to the present invention. cv2.adaptiveThreshold(image, 255 ,cv2.ADAPTIVE_THRESH_MEAN_C,cv2.THRESH_BINARY, 11 , -4 ) Conditional expression (4)

[0119] [Method for manufacturing microporous membranes] Microporous membranes were manufactured using the polyethylene powders obtained in Examples 1-7 and Comparative Examples 1-7 as follows. When the total amount of polyethylene powder and liquid paraffin is 100 parts by mass, 30 parts by mass of polyethylene powder and 70 parts by mass of liquid paraffin (liquid paraffin manufactured by MORESCO Corporation (product name: Smoil P-350P)) are added, and 1 part by mass of antioxidant (tetrakis[methylene(3,5-di-t-butyl-4-hydroxy-hydrocinnamate)]methane manufactured by Great Lakes Chemical Japan Co., Ltd. (product name: ANOX20)) is added, and the melting point (T) of the polyethylene powder is adjusted. m2 A slurry-like liquid was prepared by stirring at a temperature 30°C lower than the specified temperature for 30 minutes.

[0120] The resulting slurry liquid was placed into a Laboplast Mill (model: 4C150-01) manufactured by Toyo Seiki Co., Ltd., kneaded at a constant temperature of 200°C for 10 minutes at a screw rotation speed of 50 rpm, then hot-pressed at 180°C / 1 MPa / 3 minutes, then hot-pressed again at 180°C / 10 MPa / 2 minutes, and finally cooled-pressed at 25°C / 10 MPa / 5 minutes to form a gel sheet. The thickness of the gel sheet was adjusted to 1.0 mm by using a metal frame with a thickness of 1.0 mm.

[0121] This gel-like sheet was stretched 7x7 times at 115°C using a simultaneous biaxial stretcher. The stretched film was then cut into approximately 30cm squares and fixed in a metal frame with an inner dimension of 25cm square. After that, it was immersed in hexane to extract and remove the liquid paraffin, and then dried for more than 24 hours. Finally, it was heat-set at 134°C for 1 minute to obtain a microporous film.

[0122] [Puncture strength of microporous membranes converted to basis weight (gf / (g / m 2 )) Using a handheld compression tester "KES-G5" manufactured by Kato Tech Co., Ltd., the microporous membrane described above was fixed in a sample holder with an opening diameter of 10 mm. Next, a puncture test was performed on the center of the fixed microporous membrane with a needle tip radius of curvature of 0.5 mm and a puncture speed of 10 mm / min to obtain the puncture strength (gf) as the maximum puncture load. The obtained puncture strength (gf) was divided by the basis weight to obtain the puncture strength (gf / (g / m²)). 2The puncture strength (gf / (g / m²)) (hereinafter also simply referred to as puncture strength) was calculated. This procedure was performed eight times on eight microporous membranes, and the average value of the eight measurements was used to calculate the base weight equivalent strength (gf / (g / m²)). 2 The following criteria were used for evaluation. (Evaluation Criteria) ◎: Puncture strength equivalent to basis weight is 65 gf / (g / m 2 That's all. ○: Puncture strength equivalent to basis weight is 55 gf / (g / m 2 ) or more 65gf / (g / m 2 It is less than ). ×: Puncture strength equivalent to basis weight is 55 gf / (g / m 2 It is less than ).

[0123] [Thermal shrinkage rate of microporous membranes] When manufacturing the microporous membrane described above, the heat-fixing conditions were carried out under four conditions: 130°C / 1 min, 132°C / 1 min, 134°C / 1 min, and 136°C / 1 min. The porosity of the resulting heat-fixed membrane was calculated. The porosity was calculated by cutting a 10 cm × 10 cm square sample from the microporous membrane and measuring its volume (cm³). 3 Calculate the weight and mass (g), and then compare them with the membrane density (g / cm³). 3 The following formula was used to calculate it. Porosity (%) = (Volume - Mass / Density) / Volume × 100

[0124] Furthermore, each of the heat-fixed films was sandwiched between sheets of paper, the bundle of papers was placed in an envelope, and heated at 120°C for 1 hour. After that, it was cooled at room temperature for 15 minutes, the length of the film side was measured with a square ruler, and the thermal shrinkage rate was calculated by calculating the shrinkage rate from the original length. A graph of porosity and thermal shrinkage rate was then created, and the thermal shrinkage rate at 50% porosity was estimated from the graph. Based on the obtained thermal shrinkage rate, the superiority or inferiority of the film properties was evaluated according to the following criteria. (Evaluation Criteria) ◎: The thermal shrinkage rate is less than 20%. ○: The thermal shrinkage rate is 20% or more but less than 25%. ×: The thermal shrinkage rate is 25% or more.

[0125] [Film manufacturing method] The polyethylene powder obtained in Example 9 and Comparative Example 9 was molded using a T-die film-making machine (HM40N, manufactured by Hokushin Sangyo Co., Ltd., screw diameter 40 mm, die width 300 mm) at a cylinder temperature of 200°C, a die temperature of 210°C, and an extrusion rate of 5 kg / hour. 50 mm was trimmed from both ends to obtain a film with a thickness of 35 μm.

[0126] [Evaluation of film transparency] The haze value of the above film was measured using a HAZEMETER HM-150 manufactured by Murakami Color Technology Laboratory Co., Ltd., in accordance with ASTM D1003. A smaller haze value indicates better transparency. (Evaluation Criteria) ◎: The haze value is less than 20%. ○: The haze value is between 20% and 30%. ×: The haze value is 30% or higher.

[0127] [Method for manufacturing high-strength fibers] High-strength fibers were manufactured using the polyethylene powder obtained in Example 8 and Comparative Example 8 as follows. When the total amount of polyethylene powder and liquid paraffin was 100 parts by mass, 7 parts by mass of polyethylene powder, 93 parts by mass of liquid paraffin (liquid paraffin manufactured by MORESCO Corporation (product name: Smoil P-350P)), and 1 part by mass of antioxidant (tetrakis[methylene(3,5-di-t-butyl-4-hydroxy-hydrocinnamate)]methane manufactured by Great Lakes Chemical Japan Co., Ltd. (product name: ANOX20)) were mixed and stirred for 30 minutes at a temperature 30°C lower than the melting point (Tm2) of the polyethylene powder to prepare a slurry-like liquid. Next, the slurry-like liquid was fed into a twin-screw extruder (model: 2D25S) for a Laboplast Mill (model: 4C150) manufactured by Toyo Seiki Co., Ltd., and kneaded at a constant temperature of 200°C.

[0128] The yarn was then passed through a spinneret attached to the tip of the extruder and spun. The spinneret temperature was 200°C, the discharge rate was 300g / hour, and the pore size of the spinneret was 1.0mm. Next, the yarn containing the extruded liquid paraffin was wound up at a speed of 50 m / min at a distance of 2.0 m from the spinneret under room temperature conditions.

[0129] Next, in order to remove the liquid paraffin from the wound thread, the thread was immersed in hexane for extraction, and then dried for more than 24 hours. The obtained yarn was first stretched at a speed of 20 mm / min in a constant temperature bath set to 120°C, and then secondarily stretched at a speed of 10 mm / min in a constant temperature bath set to 140°C until just before the yarn broke, thereby obtaining high-strength fibers (stretched yarn).

[0130] [Tensile breaking strength of high-strength fibers] Ten meters of high-strength fibers (drawn yarn) spun using the method described above were cut at 1-meter intervals. Ten of the resulting fibers were then pulled until they broke under room temperature conditions, and the average breaking strength was calculated. The breaking strength was calculated by dividing the maximum load applied to the yarn by its fineness. The fineness was 1 × 10⁶ of the yarn. 4 The weight is per meter and is expressed in units of dtex. The tensile breaking strength of high-strength fibers was evaluated according to the following criteria. (Evaluation Criteria) ◎: Tensile breaking strength is 30 cN / dtex or higher. ○: Tensile breaking strength is 25 cN / dtex or more, and less than 30 cN / dtex. ×: Tensile breaking strength is less than 25 cN / dtex.

[0131] [Example 1] ([D] Preparation of inorganic solid particles with adsorbed liquid components [A]) 2,000 mL of a hexane solution of 1 mol / L Mg6(C4H9)12AL(C2H5)3 (hereinafter abbreviated as "Mg1") (equivalent to 2,000 mmol of magnesium and aluminum) was charged into an 8 L stainless steel autoclave purged with nitrogen. 146 mL of a 5.47 mol / L n-butanol hexane solution was added dropwise over 3 hours while stirring at 50°C. After completion, the line was washed with 300 mL of hexane. Stirring was then continued at 50°C for 2 hours. After the reaction was complete, the mixture was cooled to room temperature and used as the starting material (b-1). The magnesium concentration of starting material (b-1) was 0.704 mol / L.

[0132] 1,000 mL of a hexane solution of 1 mol / L hydroxytrichlorosilane was charged into an 8 L stainless steel autoclave purged with nitrogen. 1,340 mL of a hexane solution of the organomagnesium compound (b-1) (equivalent to 943 mmol of magnesium) was added dropwise over 3 hours at 65°C, and the reaction was continued for 1 hour at 65°C with stirring. After the reaction was complete, the supernatant was removed and washed four times with 1,800 mL of hexane to obtain the (B-1) support. Analysis of this support revealed that it contained 7.5 mmol of magnesium per gram of solid. To 3,000 mL of hexane slurry containing 133 g of the above raw material (B-1) carrier, 800 mmol of 1-butanol (manufactured by Tokyo Chemical Industry Co., Ltd.) was added dropwise over 1 hour at 50°C, and the reaction was continued for another hour at 65°C with stirring. After the reaction was complete, the supernatant was removed and washed four times with 1,800 mL of hexane to obtain the raw material (B-2) carrier.

[0133] To 3,000 mL of hexane slurry containing 133 g of the above raw material (B-2) carrier, 1,200 mmol of diethylaluminum chloride (1.2 mol / L, hexane solution [manufactured by Tosoh Finechem Co., Ltd.]) was added dropwise over 1 hour at 65°C, and the reaction was continued for another hour at 65°C with stirring. After the reaction was complete, the supernatant was removed and washed four times with 1,800 mL of hexane to obtain [A] inorganic solid particles.

[0134] The resulting slurry was kept at 60°C under stirring, and 200 ml of modified methylaluminoxane (1 mol / L, m / n=3, MMAO hexane solution [manufactured by Tosoh Finechem Co., Ltd.]) was added. The reaction was then continued for 2 hours with stirring. After the reaction was complete, the supernatant was removed and washed four times with 1,800 mL of hexane to obtain 2,700 mL of hexane slurry containing 156 g of [A] inorganic solid particles from which the [D] liquid component had been adsorbed.

[0135] ([B] Preparation of transition metal compound components) [B] As the transition metal compound component, [(Nt-butylamide)(tetramethyl-η5-cyclopentadienyl)dimethylsilane]titanium-1,3-pentadiene (hereinafter abbreviated as "titanium complex α") was used. 200 mmol of the titanium complex was dissolved in 1000 ml of isopar E [Exxon Chemicals], and 40 ml of a hexane solution of Mg1 (concentration 1 M) was added as an organomagnesium compound. Further hexane was added to adjust the titanium complex concentration to 0.1 M, and the [B] transition metal compound component was obtained. This Mg1 was synthesized by mixing a predetermined amount of triethylaluminum and dibutylmagnesium in hexane at 25°C.

[0136] ([C] Preparation of activator) [C] Bis(tulose alkyl hydride)methylammonium-tris(pentafluorophenyl)(4-hydroxyphenyl)borate (hereinafter abbreviated as "borate") was used as the activator. Ethoxydiethylaluminum was used as the organoaluminum compound (C-2).

[0137] 17.8 g of borate was added to 156 ml of toluene and dissolved to obtain a 100 mM toluene solution of borate. To this toluene solution of borate, 15.6 ml of hexane solution of ethoxydiethylaluminum (concentration 1 M) was added at 25°C, and further hexane was added to adjust the borate concentration in the toluene solution to 80 mM. Subsequently, the [C] activator was prepared by stirring at 25°C for 1 hour.

[0138] (Preparation of polyethylene polymerization catalyst) To 2700 ml of a slurry of inorganic solid particles [A] on which the liquid component [D] obtained by the above procedure was adsorbed, 195 ml of the activator [C] obtained by the above procedure and 156 ml of the transition metal compound component [B] were simultaneously added from a separate line using a metering pump while stirring at 25°C. The reaction was then continued for 2 hours to prepare a polyethylene polymerization catalyst. The addition time for both the activator [C] and the transition metal compound component [B] was 30 minutes, and the stirring speed was 400 rpm.

[0139] (Preparation of liquid component [E]) The aforementioned Mg1 was used as the organomagnesium compound [E-1]. Methylhydropolysiloxane (viscosity 20 centistokes at 25°C) was used as compound [E-2]. In a 200 ml flask, 40 ml of hexane and Mg1 were added while stirring, with a total amount of Mg and Al of 38.0 mmol. Then, 40 ml of hexane containing 2.27 g (37.8 mmol) of methylhydropolysiloxane was added while stirring at 20°C. The temperature was then raised to 80°C and the reaction was carried out under stirring for 3 hours to prepare liquid component [E].

[0140] Here, the polymerization of ethylene was carried out as follows. First, 800 ml of hexane was placed in a 1.5 L autoclave, and 0.25 mmol of the above liquid component [E] was added as the total amount of Mg and Al. Pressurized ethylene was then added to this autoclave, and the internal pressure of the autoclave was increased to 0.8 MPa. Next, the internal temperature of the autoclave was increased to 70°C, and a slurry of polyethylene polymerization catalyst heated to 85°C was added to the autoclave simultaneously with modified methylaluminoxane (1 mol / L, m / n=3, MMAO hexane solution [manufactured by Tosoh Finechem Co., Ltd.]) at a ratio of 50 mmol (molar ratio, Al / Al+Ti) to a total of 2.8 mmol in terms of Ti, thereby initiating the polymerization of ethylene. In addition, while adding ethylene to the autoclave to maintain the total pressure of the autoclave at 0.8 MPa, 500 mol-ppm of hydrogen (hydrogen / (ethylene+hydrogen)) was also added, and polymerization was carried out for 1 hour. After polymerization was complete, the reaction mixture (polymer slurry) was removed from the autoclave, and the catalyst was deactivated with methanol. The reaction mixture was then filtered, washed, and dried to obtain a dry polymer powder.

[0141] [Example 2] A catalyst was prepared under the same conditions as in Example 1. The prepared catalyst was immediately dried by degassing under reduced pressure using a vacuum pump and stored in a cool, dark place at 15°C or below until used for ethylene polymerization. When used for ethylene polymerization, 2,700 ml of hexane was added to the dried catalyst under a nitrogen atmosphere. Furthermore, ethylene was polymerized under the same conditions as in Example 1, except that a slurry of polyethylene polymerization catalyst heated to 75°C was added to the autoclave in an amount equivalent to 1.0 mmol of Ti.

[0142] [Example 3] The catalyst was prepared under the same conditions as in Example 1, except that the raw material (B-1) support was used as [A] inorganic solid particles. Furthermore, ethylene was polymerized under the same conditions as in Example 1.

[0143] [Example 4] A catalyst was prepared under the same conditions as in Example 1, except that magnesium chloride powder, <200 μm (manufactured by Sigma-Aldrich) was used as [A] inorganic solid particles, and [D] a liquid component was adsorbed onto 2700 ml of magnesium chloride powder, <200 μm. [C] 98 ml of activator and [B] 78 ml of transition metal compound component were added simultaneously from a separate line using a metering pump while stirring at 25°C. Ethylene was also polymerized under the same conditions as in Example 1.

[0144] [Example 5] A catalyst was prepared under the same conditions as in Example 1. Furthermore, ethylene was polymerized under the same conditions as in Example 1, except that a slurry of polyethylene polymerization catalyst at room temperature was added to the autoclave in an amount equivalent to 1.4 mmol of Ti.

[0145] [Example 6] [B] The catalyst was prepared under the same conditions as in Example 1, except that [(Nt-butylamide)(tetramethyl-η5-cyclopentadienyl)dimethylsilane]titanium-dichloride (hereinafter abbreviated as "titanium complex β") was used as the transition metal compound component. Ethylene was polymerized under the same conditions as in Example 1.

[0146] [Example 7] 300 mL of industrial alcohol (Ekinen F-3, manufactured by Nippon Alcohol Sales Co., Ltd.) and 300 mL of distilled water were placed in a 1 L flask, 15.0 g of concentrated hydrochloric acid and 42.4 g (120 mmol) of dimethylbehenylamine (Armin DM22D, manufactured by Lion Corporation) were added, and the mixture was heated to 45°C to disperse 100 g of synthetic hectorite (Laponite RDS, manufactured by Rockwood Additives). The mixture was then heated to 60°C and stirred for 1 hour while maintaining that temperature. After filtering the slurry, it was washed twice with 600 mL of 60°C water and dried in an oven at 85°C for 12 hours to obtain 100 g of organically modified clay. This organically modified clay was ball-milled to obtain the raw material (B-5) support. The catalyst was prepared under the same conditions as in Example 1, except that the raw material (B-5) support was used as [A] inorganic solid particles. Ethylene was polymerized under the same conditions as in Example 1.

[0147] [Example 8] The catalyst was prepared under the same conditions as in Example 1. Furthermore, ethylene was polymerized under the same conditions as in Example 1, except that hydrogen was not added while ethylene was added to the autoclave while maintaining the total pressure of the autoclave at 0.8 MPa.

[0148] [Example 9] A catalyst was prepared under the same conditions as in Example 1. Furthermore, ethylene was polymerized under the same conditions as in Example 1, except that 1 mol-% (molar ratio, hydrogen / (ethylene + hydrogen)) of hydrogen was added to the autoclave while maintaining the total pressure of the autoclave at 0.8 MPa.

[0149] [Comparative Example 1] ([D] Preparation of inorganic solid particles with adsorbed liquid components [A]) 130 g of heat-treated silica (Q-6 [manufactured by Fuji Silicia Co., Ltd.]) was dispersed in 2500 ml of hexane in an 8 L autoclave purged with nitrogen to obtain a slurry. While maintaining the obtained slurry at 20°C under stirring, 200 ml of methylaluminoxane (1 mol / LMAO hexane solution [manufactured by Tosoh Finechem Co., Ltd.]) was added, and the mixture was stirred for 2 hours. After the reaction was complete, the supernatant was removed and washed four times with 1800 mL of hexane to obtain [A] inorganic solid particles with the [D] liquid component adsorbed.

[0150] ([B] Preparation of transition metal compound components) [B] As the transition metal compound component, [(Nt-butylamide)(tetramethyl-η5-cyclopentadienyl)dimethylsilane]titanium-1,3-pentadiene (hereinafter abbreviated as "titanium complex") was used. 200 mmol of the titanium complex was dissolved in 1000 ml of Isopar E [Exxon Chemicals], and 40 ml of a hexane solution (1 M concentration) of the organomagnesium compound AlMg6(C2H5)3(C4H9)12 (hereinafter abbreviated as "Mg1") was added. Further hexane was added to adjust the titanium complex concentration to 0.1 M, and the [B] transition metal compound component was obtained. This Mg1 was synthesized by mixing a predetermined amount of triethylaluminum and dibutylmagnesium in hexane at 25°C.

[0151] ([C] Preparation of activator) [C] Bis(tulose alkyl hydride)methylammonium-tris(pentafluorophenyl)(4-hydroxyphenyl)borate (hereinafter abbreviated as "borate") was used as the activator. Ethoxydiethylaluminum was used as the organoaluminum compound (C-2). 17.8 g of borate was added to 156 ml of toluene and dissolved to obtain a 100 mM toluene solution of borate. To this toluene solution of borate, 15.6 ml of hexane solution of ethoxydiethylaluminum (concentration 1 M) was added at 25°C, and further hexane was added to adjust the borate concentration in the toluene solution to 80 mM. Subsequently, the [C] activator was prepared by stirring at 25°C for 1 hour.

[0152] (Preparation of polyethylene polymerization catalyst) To 2700 ml of a slurry of inorganic solid particles [A] on which the liquid component [D] obtained by the above procedure was adsorbed, 98 ml of the activator [C] obtained by the above procedure and 78 ml of the transition metal compound component [B] were simultaneously added from a separate line using a metering pump while stirring at 25°C. The reaction was then continued for 2 hours to prepare a polyethylene polymerization catalyst. The addition time for both the activator [C] and the transition metal compound component [B] was 30 minutes, and the stirring speed was 400 rpm.

[0153] (Preparation of liquid component [E]) The aforementioned Mg1 was used as the organomagnesium compound [E-1]. Methylhydropolysiloxane (viscosity 20 centistokes at 25°C) was used as compound [E-2]. In a 200 ml flask, 40 ml of hexane and Mg1 were added while stirring, with a total amount of Mg and Al of 38.0 mmol. Then, 40 ml of hexane containing 2.27 g (37.8 mmol) of methylhydropolysiloxane was added while stirring at 20°C. The temperature was then raised to 80°C and the reaction was carried out under stirring for 3 hours to prepare liquid component [E].

[0154] The polymerization of ethylene was carried out as follows. First, 800 ml of hexane was placed in a 1.5 L autoclave, and 0.25 mmol of the above liquid component [E] was added as the total amount of Mg and Al. Pressurized ethylene was then added to this autoclave, and the internal pressure of the autoclave was increased to 0.8 MPa. Next, the internal temperature of the autoclave was increased to 70°C, and a slurry of polyethylene polymerization catalyst heated to 75°C was added to the autoclave simultaneously with modified methylaluminoxane (1 mol / L, m / n=3, MMAO hexane solution [manufactured by Tosoh Finechem Co., Ltd.]) at a ratio of 50 mmol (molar ratio, Al / Al+Ti) to a total of 1.0 mmol in terms of Ti, thereby initiating the polymerization of ethylene. In addition, while adding ethylene to the autoclave to maintain the total pressure of the autoclave at 0.8 MPa, 500 mol-ppm of hydrogen (hydrogen / (ethylene + hydrogen)) was also added, and polymerization was carried out for 1 hour. After polymerization was complete, the reaction mixture (polymer slurry) was removed from the autoclave, and the catalyst was deactivated with methanol. The reaction mixture was then filtered, washed, and dried to obtain a dry polymer powder.

[0155] [Comparative Example 2] 2,000 mL of a hexane solution of 1 mol / L Mg6(C4H9)12AL(C2H5)3 (equivalent to 2,000 mmol of magnesium and aluminum) was charged into an 8 L stainless steel autoclave purged with nitrogen. 146 mL of a 5.47 mol / L n-butanol hexane solution was added dropwise over 3 hours while stirring at 50°C. After completion, the line was washed with 300 mL of hexane. Stirring was then continued at 50°C for 2 hours. After the reaction was complete, the mixture was cooled to room temperature and used as the starting material (b-1). The magnesium concentration of starting material (b-1) was 0.704 mol / L.

[0156] 1,000 mL of a hexane solution of 1 mol / L hydroxytrichlorosilane was charged into an 8 L stainless steel autoclave purged with nitrogen. 1,340 mL of a hexane solution of the organomagnesium compound (b-1) (equivalent to 943 mmol of magnesium) was added dropwise over 3 hours at 65°C, and the reaction was continued for 1 hour at 65°C with stirring. After the reaction was complete, the supernatant was removed and washed four times with 1,800 mL of hexane to obtain the (B-1) support. Analysis of this support revealed that it contained 7.5 mmol of magnesium per gram of solid. 2,000 mL of a hexane solution of 1 mol / L Mg6(C4H9)12Al(C2H5)3 (equivalent to 2,000 mmol of magnesium and aluminum) was charged into an 8 L stainless steel autoclave that had been thoroughly purged with nitrogen. While stirring at 80°C, 240 mL of a hexane solution of 8.33 mol / L methylhydrodiene polysiloxane (manufactured by Shin-Etsu Chemical Co., Ltd.) was pumped in, and stirring was continued at 80°C for 2 hours. After the reaction was complete, the mixture was cooled to room temperature and used as the starting material [b-2]. The total concentration of magnesium and aluminum in the starting material [b-2] was 0.786 mol / L.

[0157] To 3,000 mL of hexane slurry containing 133 g of the above raw material (B-1) carrier, 800 mmol of 1-butanol (manufactured by Tokyo Chemical Industry Co., Ltd.) was added dropwise over 1 hour at 50°C, and the reaction was continued for another hour at 65°C with stirring. After the reaction was complete, the supernatant was removed and washed four times with 1,800 mL of hexane to obtain the raw material (B-2) carrier.

[0158] To 3,000 mL of hexane slurry containing 133 g of the above raw material (B-2) support, 1,200 mmol of diethylaluminum chloride (manufactured by Tosoh Finechem Co., Ltd.) was added dropwise over 1 hour at 65°C, and the reaction was continued for another hour at 65°C with stirring. After the reaction was complete, the supernatant was removed and washed four times with 1,800 mL of hexane to obtain the raw material (B-3) support. To 1,970 mL of hexane slurry containing 110 g of the above-mentioned [B-3] carrier, 103 mL of a hexane solution of 1 mol / L titanium tetrachloride and 131 mL of the raw material [b-2] were simultaneously added over 3 hours while stirring at 10°C. After the addition, the reaction was continued at 10°C for 1 hour. After the reaction was complete, the supernatant was removed and unreacted raw material components were removed by washing four times with hexane to prepare the polyethylene polymerization catalyst.

[0159] The polymerization of ethylene was carried out as follows. First, 800 ml of hexane was placed in a 1.5 L autoclave, and 0.25 mmol of the above liquid component [E] was added as the total amount of Mg and Al. Pressurized ethylene was then added to this autoclave, and the internal pressure of the autoclave was increased to 0.8 MPa. Next, the internal temperature of the autoclave was increased to 70°C, and the polymerization of ethylene was started by adding a slurry of polyethylene polymerization catalyst at room temperature to the autoclave in an amount equivalent to 1.0 mmol of Ti. While adding ethylene to the autoclave to maintain the total pressure of the autoclave at 0.8 MPa, 10 mol% of hydrogen (molar ratio, hydrogen / (ethylene + hydrogen)) was also added, and polymerization was carried out for 1 hour. After the polymerization was completed, the reaction mixture (polymer slurry) was removed from the autoclave, and the catalyst was deactivated with methanol. Subsequently, the reaction mixture was filtered, washed, and dried to obtain a dry polymer powder.

[0160] [Comparative Example 3] The catalyst was prepared under the same conditions as in Example 4. Furthermore, ethylene was polymerized under the same conditions as in Example 4, except that a slurry of polyethylene polymerization catalyst, temperature-controlled at 75°C, was added to the autoclave in an amount equivalent to 1.4 mmol of Ti.

[0161] [Comparative Example 4] [D] A catalyst was prepared under the same conditions as in Comparative Example 3, except that 400 ml of [C] activator and 305 ml of [B] transition metal compound component were simultaneously added to 2700 ml of magnesium chloride powder, <200 μm slurry, on which the liquid component had been adsorbed, using a metering pump from a separate line while stirring at 25°C. Furthermore, ethylene was polymerized under the same conditions as in Comparative Example 3, except that a slurry of polyethylene polymerization catalyst at room temperature was added to the autoclave in an amount equivalent to 1.4 mmol of Ti.

[0162] [Comparative Example 5] [B] Diphenylmethylene (cyclopentadienyl)(2-(dimethylamino)-9-fluorenyl)titanium dichloride (hereinafter abbreviated as "titanium complex γ") was used as the transition metal compound component, and the catalyst was prepared under the same conditions as in Comparative Example 3, except that 195 ml of [C] activator and 156 ml of [B] transition metal compound component were simultaneously added to 2700 ml of magnesium chloride powder, <200 μm slurry, on which the liquid component had been adsorbed, using a metering pump from a separate line while stirring at 25°C. Furthermore, ethylene was polymerized under the same conditions as in Comparative Example 3, except that a slurry of polyethylene polymerization catalyst at room temperature was added to the autoclave in an amount equivalent to 1.0 mmol of Ti.

[0163] [Comparative Example 6] [B] The catalyst was prepared under the same conditions as in Comparative Example 5, except that the following titanium complex δ was used as the transition metal compound component. Furthermore, ethylene was polymerized under the same conditions as in Comparative Example 5, except that the slurry of polyethylene polymerization catalyst at room temperature was added to the autoclave in an amount equivalent to 1.4 mmol of Ti. [ka]

[0164] [Comparative Example 7] [B] The catalyst was prepared under the same conditions as in Comparative Example 3, except that titanium complex β was used as the transition metal compound component. Furthermore, ethylene was polymerized under the same conditions as in Comparative Example 5, except that a slurry of polyethylene polymerization catalyst, temperature-controlled to 75°C, was added to the autoclave in an amount equivalent to 1.0 mmol of Ti.

[0165] [Comparative Example 8] The catalyst was prepared under the same conditions as in Comparative Example 1. Furthermore, the ethylene was polymerized under the same conditions as in Comparative Example 1, except that hydrogen was not added while ethylene was added to the autoclave to maintain the total pressure of the autoclave at 0.8 MPa.

[0166] [Comparative Example 9] A catalyst was prepared under the same conditions as in Comparative Example 1. Furthermore, ethylene was polymerized under the same conditions as in Comparative Example 1, except that 1 mol-% (molar ratio, hydrogen / (ethylene + hydrogen)) of hydrogen was added to the autoclave while maintaining the total pressure of the autoclave at 0.8 MPa.

[0167] [Evaluation of polymers] Using the obtained polyethylene powder, microporous membranes, fibers, and films were manufactured using the above manufacturing method. The puncture strength and thermal shrinkage rate of the microporous membranes, the tensile breaking strength of the fibers, and the transparency of the films were evaluated using the above evaluation method. The obtained physical property evaluation results are shown in Table 1.

[0168] [Table 1] [Industrial applicability]

[0169] By using the polyethylene powder of the present invention, it is possible to provide films with excellent transparency, fibers with superior mechanical strength, and battery separators, making it highly effective industrially and widely applicable.

Claims

1. When the sample was processed under the following <Processing Conditions> and heated and cooled under the following <Measurement Conditions> using a hot stage, the spherulites observed at the extrapolated crystallization onset temperature + 2.0°C were observed under an optical microscope. The average circularity of the spherulites is 0.3 or more and 0.7 or less, The average skewness of the circularity of the spherulite is -1 or more and 1 or less. Polyethylene powder. <Processing conditions> (1) Compression mold at a temperature above the melting point of the polyethylene powder to a thickness of 1 mm. (2) A test piece having a thickness of 15 μm is cut out from the cross section of the molded product. (3) The test piece is sandwiched between a slide glass and a cover glass, and heated again at a temperature above the melting point of the polyethylene powder to obtain a specimen for observation. <Measurement conditions> (1) The temperature is increased from 30° C. to 180° C. at a rate of 20° C. / min. (2) Hold at 180°C for 5 minutes. (3) The temperature is decreased from 180° C. to 140° C. at a rate of 20° C. / min. (4) The temperature is decreased from 140° C. to 115° C. at a rate of 2° C. / min.

2. The average area of ​​the spherulite is 20 μm 2 100 μm or more 2 Below is the The polyethylene powder according to claim 1.

3. The titanium content is less than 3 ppm. The polyethylene powder according to claim 1 or 2.

4. The magnesium content is 10 ppm or more and less than 200 ppm. The polyethylene powder according to claim 1 or 2.

5. The silica content is less than 10 ppm. The polyethylene powder according to claim 1 or 2.

6. The molecular weight distribution (Mw / Mn) is less than 4; The polyethylene powder according to claim 1 or 2.

7. A microporous membrane made of polyethylene powder, The polyethylene powder was processed under the following <Processing Conditions>, and when the powder was heated and cooled using a hot stage under the following <Measurement Conditions>, the spherulites observed at the extrapolated crystallization onset temperature + 2.0°C were as follows: The average circularity of the spherulites is 0.3 or more and 0.7 or less, The average skewness of the circularity of the spherulite is -1 or more and 1 or less, The microporous membrane has a puncture strength calculated based on basis weight of 55 gf / (g / m2) or more. Microporous membrane. <Processing conditions> (1) Compression mold at a temperature above the melting point of the polyethylene powder to a thickness of 1 mm. (2) A test piece having a thickness of 15 μm is cut out from the cross section of the molded product. (3) The test piece is sandwiched between a slide glass and a cover glass, and heated again at a temperature above the melting point of the polyethylene powder to obtain a specimen for observation. <Measurement conditions> (1) The temperature is increased from 30° C. to 180° C. at a rate of 20° C. / min. (2) Hold at 180°C for 5 minutes. (3) The temperature is decreased from 180° C. to 140° C. at a rate of 20° C. / min. (4) The temperature is decreased from 140° C. to 115° C. at a rate of 2° C. / min.

8. The thermal shrinkage rate of the microporous membrane is less than 25%. The microporous membrane of claim 7.

9. In a wet method using a solvent, The method includes an extrusion step, a stretching step, an extraction step, and a drying step, The extrusion step is a step of extruding using an extruder equipped with a T-die. A method for producing the microporous membrane according to claim 7 or 8.

10. A high strength fiber made of polyethylene powder, The polyethylene powder was processed under the following <Processing Conditions>, and when the powder was heated and cooled using a hot stage under the following <Measurement Conditions>, the spherulites observed at the extrapolated crystallization onset temperature + 2.0°C were as follows: The average circularity of the spherulites is 0.3 or more and 0.7 or less, The average skewness of the circularity of the spherulite is -1 or more and 1 or less, The tensile breaking strength of the high strength fiber is 25 cN / dtex or more. High strength fiber. <Processing conditions> (1) Compression mold at a temperature above the melting point of the polyethylene powder to a thickness of 1 mm. (2) A test piece having a thickness of 15 μm is cut out from the cross section of the molded product. (3) The test piece is sandwiched between a slide glass and a cover glass, and heated again at a temperature above the melting point of the polyethylene powder to obtain a specimen for observation. <Measurement conditions> (1) The temperature is increased from 30° C. to 180° C. at a rate of 20° C. / min. (2) Hold at 180°C for 5 minutes. (3) The temperature is decreased from 180° C. to 140° C. at a rate of 20° C. / min. (4) The temperature is decreased from 140° C. to 115° C. at a rate of 2° C. / min.

11. A method for producing the high strength fiber according to claim 10, comprising the steps of: a mixing step of stirring liquid paraffin and the polyethylene powder at a temperature 30° C. lower than the melting point (T m2 ) of the polyethylene powder to prepare a slurry liquid; A kneading step of kneading the slurry liquid to obtain a kneaded product; A yarn spinning process for spinning the kneaded mixture into yarn containing liquid paraffin using an extruder; A liquid paraffin removal step of immersing the yarn obtained in the yarn step in hexane to remove the liquid paraffin from the yarn; and A step of secondarily drawing the yarn after removing the liquid paraffin in a thermostatic bath; The method comprising:

12. A film made of polyethylene powder, The polyethylene powder was processed under the following <Processing Conditions>, and when the powder was heated and cooled using a hot stage under the following <Measurement Conditions>, the spherulites observed at the extrapolated crystallization onset temperature + 2.0°C were as follows: The average circularity of the spherulites is 0.3 or more and 0.7 or less, The average skewness of the circularity of the spherulite is -1 or more and 1 or less, The haze value of the film according to ASTM D1003 is less than 30%; film. <Processing conditions> (1) Compression mold at a temperature above the melting point of the polyethylene powder to a thickness of 1 mm. (2) A test piece having a thickness of 15 μm is cut out from the cross section of the molded product. (3) The test piece is sandwiched between a slide glass and a cover glass, and heated again at a temperature above the melting point of the polyethylene powder to obtain a specimen for observation. <Measurement conditions> (1) The temperature is increased from 30° C. to 180° C. at a rate of 20° C. / min. (2) Hold at 180°C for 5 minutes. (3) The temperature is decreased from 180° C. to 140° C. at a rate of 20° C. / min. (4) The temperature is decreased from 140° C. to 115° C. at a rate of 2° C. / min.